Adhesive sheet

By using acrylic polymers with heptyl acrylate as a monomer component, the problems of rebound resistance and impact resistance of existing adhesive sheets when used in high temperature and high humidity environments and complex shape surfaces are solved, and high-level bonding is achieved performance.

CN119421937AActive Publication Date: 2025-02-11NITTO DENKO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202280097496.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2022-12-12
Publication Date
2025-02-11
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

When used in high temperature and high humidity environments and complex surfaces, it is difficult to achieve high levels of rebound resistance and impact resistance at the same time.

Method used

The acrylic polymer containing heptane acrylate as a monomer component is used as the material for the adhesive layer to ensure that the energy storage modulus G' at 65°C reaches 20,000 Pa or more, and the tanδ at -20°C reaches 0.3 or more.

Benefits of technology

It achieves good rebound resistance to continuous loads in the Z-axis direction under high temperature and high humidity environment, and shows excellent impact resistance on complex-shaped surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119421937A_ABST
    Figure CN119421937A_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive sheet capable of achieving both resilience resistance and impact resistance at a high level. The pressure-sensitive adhesive sheet has a pressure-sensitive adhesive layer containing an acrylic polymer. The acrylic polymer is a polymer containing a monomer component of heptyl acrylate. In addition, the storage modulus G'of the adhesive layer at 65 DEG C is 20000 Pa or more, and the tan [delta] at-20 DEG C is 0.3 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet.

[0002] This application claims priority based on Japanese Patent Application No. 2022-108023 filed on July 4, 2022, and the entire contents of this application are incorporated herein by reference. Background Art

[0003] Typically, adhesives (also referred to as pressure-sensitive adhesives, the same below) are in a soft solid (viscoelastic) state within a temperature range near room temperature, and have the property of being adhered to an adherend by pressure. Utilizing this property, adhesives are widely used in various industrial fields, from portable electronic devices such as smartphones, home appliances to automobiles, OA equipment, etc., typically in the form of adhesive sheets containing an adhesive layer, for the purposes of bonding of components, surface protection, etc. As technical documents related to adhesive sheets, Patent Document 1 and Patent Document 2 can be cited. Patent Document 1 and Patent Document 2 describe adhesives containing acrylic polymers polymerized using heptyl acrylate as a monomer component.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2021 / 125247

[0007] Patent Document 2: International Publication No. 2021 / 125278 Summary of the invention

[0008] Problems to be solved by the invention

[0009] For adhesive sheets, various performances are required according to the application part, the mode of use, etc. For example, the fixing of components in portable electronic devices based on adhesive sheets is limited by size, weight, etc., and usually its adhesive area is small. The adhesive sheet used in this application needs to have an adhesive force that can achieve good fixing even with a small area, and from the requirements of lightweight and miniaturization, its required performance is at a higher level. In particular, portable electronic devices with touch panel displays represented by smart phones are being large-screened from the perspective of miniaturization and thinning of the product itself, and from the perspective of visual recognition and operability of the display. Due to its unique situation, the adhesive used requires adhesive fixing performance under more stringent conditions. Specifically, in this application, of course, the adhesive area is limited, for example, elastic components such as flexible printed wiring boards (FPCs) are bent and accommodated in a limited internal space in a portable electronic device, and it is positioned and stably fixed with an adhesive sheet with high precision. In an adhesive sheet used to fix such components, since a continuous peel load is applied in the thickness direction (also called the Z-axis direction) of the adhesive sheet, it is required to have resilience that can continuously resist the elastic repulsion of the above-mentioned components (specifically, durability against a continuous peel load in the thickness direction (Z-axis direction) of the adhesive sheet).

[0010] In addition, in recent years, in addition to the above-mentioned lightweight and miniaturization, the development of portable electronic device products with curved shapes such as three-dimensional shapes has been continuously developed, and its surface shape has a tendency to become more complicated. For adhesive sheets attached to complex shapes, it is required to follow its shape and adhesion performance well. For example, in the above-mentioned portable electronic devices, for adhesive sheets for fixing components such as protective glass with complex surface shapes (which may be curved shapes), there is a tendency to apply a continuous peeling load larger than before, and for adhesive sheets used for such purposes, a higher level of resistance to continuous peeling load is required.

[0011] Furthermore, the temperature and humidity in the portable electronic device are affected not only by the heat in the electronic device but also by the external environment, and may reach a high temperature exceeding 50°C or a high humidity. An adhesive for this purpose is required to exhibit stable repulsion resistance in the Z-axis direction even in such an environment.

[0012] In addition, portable electronic devices have the danger of falling from the perspective of their use, so for the adhesive used in portable electronic devices, it is strongly required to improve the impact resistance. Impact resistance can be improved by reducing the elastic modulus of the adhesive. For example, when it is designed to reduce the elastic modulus of the adhesive by reducing the degree of crosslinking, the cohesive force required for the resilience resistance is also reduced, and it is difficult to obtain good resilience resistance. It can be seen that resilience resistance and impact resistance are contradictory characteristics and are difficult to achieve simultaneously. It is meaningful if a kind of adhesive sheet can be provided that also shows good resilience resistance (resistance to the continuous load in the Z-axis direction) and excellent impact resistance even under harsh environments such as high temperature and high humidity conditions for the continuous peeling load in the above-mentioned thickness direction.

[0013] The inventors have conducted intensive research and found that, in a structure using an acrylic polymer containing heptyl acrylate as a monomer component, an adhesive having good repulsion resistance to a continuous load in the Z-axis direction and excellent impact resistance can be obtained even in a harsh environment, thereby completing the present invention. That is, the object of the present invention is to provide a PSA sheet that can simultaneously achieve high levels of repulsion resistance and impact resistance.

[0014] Means used to solve problems

[0015] According to the present specification, a pressure-sensitive adhesive sheet is provided. The pressure-sensitive adhesive sheet has a pressure-sensitive adhesive layer containing an acrylic polymer. The acrylic polymer is a polymer containing a monomer component of heptyl acrylate. In addition, the pressure-sensitive adhesive layer has a storage modulus G' of 20,000 Pa or more at 65°C, and a tanδ of 0.3 or more at -20°C. Here, tanδ refers to the ratio of the loss modulus G" of the pressure-sensitive adhesive layer to the storage modulus G' (G" / G').

[0016] According to the above-mentioned structure, the 65°C storage modulus of the adhesive layer is 20000Pa or more, so it can exert good anti-rebound elasticity. In addition, the -20°C tanδ of the adhesive layer is 0.3 or more, so it is easy to obtain excellent impact resistance. The above-mentioned 65°C storage modulus G' and -20°C tanδ can be appropriately achieved by using an acrylic polymer containing heptyl acrylate as a monomer component. According to the adhesive sheet of the above-mentioned structure, it is possible to achieve high levels of anti-rebound elasticity and impact resistance at the same time.

[0017] In some preferred embodiments, the weight average molecular weight (Mw) of the acrylic polymer is 700,000 or more. By using an acrylic polymer containing heptyl acrylate as a monomer unit and having a Mw of 700,000 or more, the above-mentioned viscoelastic properties (specifically, 65°C storage modulus G' and -20°C tanδ) can be preferably satisfied, and it is easy to achieve both high levels of repulsion resistance and impact resistance.

[0018] In some preferred embodiments, the glass transition temperature (Tg) of the adhesive layer is in the range of -15°C to 15°C. Here, the glass transition temperature of the adhesive layer refers to the glass transition temperature obtained from the peak temperature of tanδ in the dynamic viscoelasticity measurement. In an adhesive layer with a Tg in the range of -15°C to 15°C, it is easy to achieve both repulsion resistance and impact resistance.

[0019] In some preferred embodiments, the adhesive layer further comprises a tackifying resin. The technology disclosed herein is preferably implemented in a configuration in which the adhesive layer comprises a tackifying resin. As the tackifying resin, at least one selected from a rosin-based tackifying resin and a terpene-based tackifying resin is preferably used. In some embodiments, the content of the tackifying resin in the adhesive layer is less than 70 parts by weight relative to 100 parts by weight of the acrylic polymer. The effect of the technology disclosed herein can preferably be achieved by appropriately adjusting the content of the tackifying resin in the adhesive layer within the above range.

[0020] In some preferred embodiments, the adhesive layer further comprises an acrylic oligomer. The technology disclosed herein is preferably implemented in a manner where the adhesive layer comprises an acrylic oligomer. Among them, it is more preferred to use a tackifying resin and an acrylic oligomer in combination.

[0021] In some preferred embodiments, the adhesive composition for forming the adhesive layer comprises at least one selected from an isocyanate crosslinking agent and an epoxy crosslinking agent. By using a crosslinking agent selected from an isocyanate crosslinking agent and an epoxy crosslinking agent, the cohesive force of the adhesive can be appropriately improved, and the rebound resistance can be satisfactorily improved while having impact resistance.

[0022] Some preferred embodiments of the PSA sheet have a 180 degree peel strength to a stainless steel plate (adhesion to SUS) of 20 N / 25 mm or more. A PSA sheet having such adhesion to SUS can exhibit excellent adhesive strength.

[0023] The adhesive sheet disclosed herein can take into account both rebound resistance and impact resistance, and is therefore preferably used for joining components of portable electronic devices that require high rebound resistance and impact resistance. As described above, according to this specification, a portable electronic device using any adhesive sheet disclosed herein is provided, in other words, a portable electronic device comprising the adhesive sheet is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to one embodiment.

[0025] Figure 2 It is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to another embodiment.

[0026] Figure 3 It is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to another embodiment.

[0027] Figure 4 This is a front view schematically showing an example of a portable electronic device including a pressure-sensitive adhesive sheet.

[0028] Figure 5 This is a schematic diagram for explaining the method of the repulsion resistance test in the Z-axis direction. DETAILED DESCRIPTION

[0029] Hereinafter, a preferred embodiment of the present invention will be described. It should be noted that matters other than those specifically mentioned in this specification and required for the implementation of the present invention can be understood by those skilled in the art based on the teachings for the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented according to the contents disclosed in this specification and the technical common sense in the art. In addition, in the following drawings, the same reference numerals are sometimes used to illustrate components / parts that play the same role, and repeated descriptions are sometimes omitted or simplified. In addition, in order to clearly illustrate the present invention, the embodiments described in the drawings are schematically illustrated and do not necessarily accurately represent the size and scale of the adhesive sheet of the present invention actually provided as a product.

[0030] In this specification, "adhesive" refers to a material that is in a soft solid (viscoelastic) state in the temperature range near room temperature as described above, and has the property of being easily adhered to an adherend by pressure. The so-called adhesive herein is defined as "CADahlquist, "Adhesion: Fundamental and Practice", McLaren & Sons, (1966) P.143", which generally has a complex tensile elastic modulus E * (1Hz)<10 7 dyne / cm 2 A material having the above properties at 25°C.

[0031] In this specification, carbon from biomass refers to carbon (renewable carbon) from biomass materials, i.e., materials from renewable organic resources. The above-mentioned biomass materials typically refer to materials from biological resources (typically plants that perform photosynthesis) that can be continuously reproduced as long as there is sunlight, water and carbon dioxide. Therefore, materials from fossil resources that have been exhausted due to use after mining (fossil resource materials) do not belong to the concept of biomass materials mentioned here. The biomass carbon ratio of the adhesive layer and the adhesive sheet, that is, the proportion of carbon from biomass in the total carbon contained in the adhesive layer and the adhesive sheet can be estimated based on the carbon isotope content of mass number 14 measured according to ASTM D6866.

[0032] <Composition of Adhesive Sheet>

[0033] The adhesive sheet disclosed herein is constituted by containing an adhesive layer. The above-mentioned adhesive sheet, for example, can be in the form of a substrate-free double-sided adhesive sheet having a first adhesive face constituted by one surface of the adhesive layer and a second adhesive face constituted by another surface of the adhesive layer. Alternatively, the adhesive sheet disclosed herein can be in the form of an adhesive sheet with a substrate obtained by laminating the above-mentioned adhesive layer on one side or both sides of a supporting substrate. Hereinafter, the supporting substrate is sometimes referred to as "substrate". It should be noted that the concept of the adhesive sheet mentioned herein may include articles referred to as adhesive tapes, adhesive labels, adhesive films, etc. It should be noted that the adhesive sheet disclosed herein can be in a roll shape or in a monolithic shape. Alternatively, it can be an adhesive sheet further processed into a form of various shapes.

[0034] The structure of a PSA sheet according to one embodiment is schematically shown in Figure 1 The adhesive sheet 1 is formed in the form of a double-sided adhesive sheet without a substrate and composed of an adhesive layer 21. The adhesive sheet 1 is used by sticking a first adhesive surface 21A composed of one surface (first surface) of the adhesive layer 21 and a second adhesive surface 21B composed of the other surface (second surface) of the adhesive layer 21 to different parts of the adherend. The parts where the adhesive surfaces 21A and 21B are stuck can be respective parts of different components or different parts within a single component. Figure 1As shown, the adhesive sheet 1 before use (i.e., before being pasted on the adherend) can be a constituent element of an adhesive sheet 100 with a release liner in which the first adhesive surface 21A and the second adhesive surface 21B are protected by release liners 31 and 32, which are at least one side opposite to the adhesive layer 21 and are respectively the release surface. As the release liners 31 and 32, for example, it is preferred to use a release liner formed in the form of a single surface being a release surface by providing a release layer formed by a release treatment agent on a single surface of a sheet-like substrate (liner substrate). Alternatively, the release liner 32 can be omitted, and a release liner 31 with two surfaces being the release surface is used, which is overlapped with the adhesive sheet 1 and wound into a spiral shape, thereby forming an adhesive sheet with a release liner in a form (rolled form) in which the second adhesive surface 21B is in contact with the back surface of the release liner 31 and is protected.

[0035] The structure of a pressure-sensitive adhesive sheet according to another embodiment is schematically shown in Figure 2 The adhesive sheet 2 is formed in the form of a single-sided adhesive sheet with a substrate, and the single-sided adhesive sheet with a substrate has: a sheet-shaped supporting substrate (e.g., a resin film) 10 having a first surface 10A and a second surface 10B, and an adhesive layer 21 provided on the first surface 10A side. The adhesive layer 21 is fixedly provided on the first surface 10A side of the supporting substrate 10, that is, it is not intended to be separated from the supporting substrate 10. Figure 2 As shown, the adhesive sheet 2 before use may be a component of an adhesive sheet 200 with a release liner in which the surface (adhesive surface) 21A of the adhesive layer 21 is protected by a release liner 31 whose at least one side opposite to the adhesive layer 21 is a release surface. Alternatively, the release liner 31 may be omitted, and a supporting substrate 10 having a second surface 10B as a release surface may be used, and the adhesive sheet 2 may be rolled up so that the adhesive surface 21A is in contact with the second surface (back surface) 10B of the supporting substrate 10 and protected (rolled form).

[0036] The structure of a pressure-sensitive adhesive sheet according to another embodiment is schematically shown in Figure 3 The adhesive sheet 3 is formed in the form of a double-sided adhesive sheet with a substrate, and the double-sided adhesive sheet with a substrate has: a sheet-shaped supporting substrate (e.g., a resin film) 10 having a first surface 10A and a second surface 10B, a first adhesive layer 21 fixedly arranged on the first surface 10A side, and a second adhesive layer 22 fixedly arranged on the second surface 10B side. Figure 3As shown, the adhesive sheet 3 before use may be a constituent element of an adhesive sheet 300 with a release liner in which the surface (first adhesive surface) 21A of the first adhesive layer 21 and the surface (second adhesive surface) 22A of the second adhesive layer 22 are protected by release liners 31 and 32. Alternatively, the release liner 32 may be omitted, and a release liner 31 having two release surfaces may be used, which is overlapped with the adhesive sheet 3 and wound into a spiral shape, thereby constituting an adhesive sheet with a release liner in which the second adhesive surface 22A is in contact with the back surface of the release liner 31 and is protected (rolled shape).

[0037] It should be noted that in the above-mentioned double-sided adhesive sheet with a substrate, at least one of the first adhesive layer and the second adhesive layer (e.g., the first adhesive layer) may be the adhesive layer described below, and the other adhesive layer (e.g., the second adhesive layer) may be the adhesive layer disclosed herein, or may be an adhesive layer having a different composition from the adhesive layer disclosed herein (specifically, the above-mentioned one adhesive layer. For example, the first adhesive layer). Such another adhesive layer may be formed, for example, from a known or commonly used adhesive.

[0038] In addition, although not particularly limited, according to the technology disclosed herein, in the formation of the foam substrate that is not conducive to improving impact resistance, it is possible to take into account both resilience and impact resistance. Therefore, the technology disclosed herein can be implemented in the form of a double-sided adhesive sheet without substrate consisting of an adhesive layer, and in the form of an adhesive sheet with a substrate with a substrate (non-foam substrate) other than the foam substrate. Wherein, the form of a double-sided adhesive sheet without substrate is preferred. The double-sided adhesive sheet without substrate can be thinned to the extent of not having substrate, and can contribute to the miniaturization and space saving of the product of the double-sided adhesive sheet. In addition, according to the adhesive sheet without substrate, the effect of the adhesive layer such as resilience and impact resistance to the continuous load in the Z-axis direction can be shown to the greatest extent.

[0039] <Adhesive Layer>

[0040] (Viscoelastic properties)

[0041] The adhesive layer disclosed herein (in the embodiment having the first adhesive layer and the second adhesive layer, unless otherwise specified, at least one of the first adhesive layer and the second adhesive layer is the same) has a storage modulus G' of 20,000 Pa or more at 65°C. According to the adhesive having the above-mentioned storage modulus at 65°C, it is easy to obtain good resilience resistance (especially resilience resistance to continuous load in the Z-axis direction under harsh environments such as high temperature conditions). In some preferred embodiments, from the viewpoint of improving resilience resistance, the above-mentioned storage modulus at 65°C is 21,000 Pa or more, can be 22,000 Pa or more, and 23,000 Pa or more is appropriate, more preferably 24,000 Pa or more, further preferably 25,000 Pa or more, particularly preferably 26,000 Pa or more, can be 27,000 Pa or more, can be 28,000 Pa or more, can be 29,000 Pa or more, can be 30,000 Pa or more, can be 31,000 Pa or more, can be 32,000 Pa or more, and can be 33,000 Pa or more. The upper limit of the 65°C storage modulus can be set within an appropriate range that can take into account both resilience resistance and impact resistance. In some embodiments, the 65°C storage modulus is appropriately about 60,000 Pa or less, preferably 50,000 Pa or less, more preferably 40,000 Pa or less, further preferably 35,000 Pa or less, and can be 32,000 Pa or less, can be 30,000 Pa or less, can be 28,000 Pa or less, and can be 26,000 Pa or less.

[0042] In addition, the adhesive layer disclosed herein is characterized in that, in addition to the above-mentioned 65°C storage modulus of 20,000 Pa or more, the tanδ at -20°C is 0.3 or more. The above-mentioned tanδ (dielectric loss tangent) refers to the ratio of the loss modulus G" of the adhesive layer to the storage modulus G' of the adhesive layer (G" / G'). -20°C corresponds to the impact velocity region when falling according to the temperature-velocity conversion rule. According to the adhesive having a tanδ of 0.3 or more at -20°C, excellent impact resistance can be easily obtained. In some embodiments, the above-mentioned -20°C tanδ is 0.35 or more, can be 0.40 or more, and can also be 0.45 or more. In some preferred embodiments, from the viewpoint of impact resistance, the above-mentioned -20°C tanδ is 0.50 or more, more preferably 0.55 or more, and further preferably 0.60 or more. The upper limit of the above-mentioned -20°C tanδ can be set within an appropriate range that can take into account both rebound resistance and impact resistance. The -20°C tanδ may be, for example, about 2 or less, 1.8 or less, 1.6 or less, or 1.4 or less. In some embodiments, the -20°C tanδ is appropriately 1.2 or less, and from the viewpoint of rebound resistance, it is preferably 1.0 or less, more preferably 0.80 or less, further preferably 0.70 or less, and may be 0.60 or less, or 0.55 or less.

[0043] Although not particularly limited, in some preferred embodiments, the glass transition temperature (Tg) of the adhesive layer is in the range of -15°C to 15°C. Here, the glass transition temperature of the adhesive layer refers to the glass transition temperature obtained from the peak temperature of tanδ in the dynamic viscoelasticity measurement. By using an adhesive having a Tg in the range of -15°C to 15°C, it is possible to satisfactorily balance the repulsion resistance and the impact resistance. From the viewpoint of repulsion resistance, the Tg of the adhesive layer is more preferably above -12°C, further preferably above -10°C, particularly preferably above -7°C, may be above -5°C, may be above -3°C, may be above -1°C, may be above 0°C (for example, greater than 0°C), may be above 1°C. In addition, from the viewpoint of impact resistance, the Tg of the adhesive layer is preferably below 12°C, more preferably below 10°C, further preferably below 7°C, particularly preferably below 5°C, may be below 3°C, may be below 1°C, may be below 0°C (for example, less than 0°C), may be below -1°C, may be below -3°C.

[0044] In the technology disclosed herein, the 65°C storage modulus, -20°C tanδ, and Tg of the adhesive layer can be determined by dynamic viscoelasticity. Specifically, a plurality of adhesive layers (adhesive sheets in the case of no substrate adhesive sheet) as the object of measurement are overlapped to make an adhesive layer with a thickness of about 2 mm. The adhesive layer is punched into a disc-shaped sample with a diameter of 7.9 mm and fixed between parallel plates, and a dynamic viscoelasticity measurement is performed under the following conditions using a viscoelasticity tester (e.g., manufactured by TA Instruments, ARES or its equivalent) to obtain 65°C storage modulus, -20°C tanδ, and Tg.

[0045] ·Measurement mode: Shear mode

[0046] Temperature range: -70℃~150℃

[0047] Heating rate: 5℃ / min

[0048] ·Measurement frequency: 1Hz

[0049] The measurement was also performed by the above method in the Examples described below. It should be noted that as the measurement object, that is, the adhesive layer, a layer formed by applying the corresponding adhesive composition in a layer form and drying or curing it can be used.

[0050] (Acrylic polymer)

[0051] The adhesive layer constituting the adhesive sheet disclosed herein comprises an acrylic polymer. The above-mentioned adhesive layer is typically an adhesive layer using an acrylic polymer as a base polymer. Such an adhesive layer is also referred to as an acrylic adhesive layer. It should be noted that the base polymer refers to the main component of the rubbery polymer (a polymer showing rubber elasticity in the temperature range near room temperature) contained in the adhesive layer. In addition, in this manual, in the absence of special description, "main component" refers to a component having a content greater than 50% by weight. In addition, the following description of the components that can be contained in adhesive and adhesive layer, as long as there is no special description, can be applied to the adhesive composition for forming an adhesive (layer).

[0052] In addition, in this specification, "acrylic polymer" refers to a polymer containing monomer units derived from a monomer having at least one (meth)acryloyl group in one molecule as monomer units constituting the polymer. Hereinafter, a monomer having at least one (meth)acryloyl group in one molecule is also referred to as an "acrylic monomer". Therefore, the acrylic polymer of this specification is defined as a polymer containing monomer units derived from acrylic monomers. It should be noted that, in this specification, "(meth)acryloyl" collectively refers to acryloyl and methacryloyl. Similarly, "(meth)acrylate" collectively refers to acrylate and methacrylate, and "(meth)acrylic acid" collectively refers to acrylic acid and methacrylic acid.

[0053] As the acrylic polymer used in the technology disclosed herein, a polymer containing a monomer component of heptyl acrylate is used. The acrylic polymer polymerized using a monomer component containing heptyl acrylate is more flexible than polymers of other alkyl acrylates such as n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA), so the adhesive containing the polymer is likely to have a high value of tanδ at -20°C, and is likely to obtain excellent impact resistance. The reason is not particularly restrictive, but it is believed that the polymer containing heptyl acrylate as a monomer unit has a relatively large space between the main chains in the adhesive in addition to a low glass transition temperature. Among the heptyl acrylates, n-heptyl acrylate is preferred from the viewpoint of flexibility. The acrylic polymer synthesized by containing n-heptyl acrylate as a monomer component has a relatively long straight-chain side chain, so it is believed that the space between the main chains is likely to become larger.

[0054] In some embodiments, the proportion of heptyl acrylate in the monomer component of the acrylic polymer is, for example, 50% by weight or more (for example, greater than 50% by weight), preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 85% by weight or more, particularly preferably 90% by weight or more, 92% by weight or more, 94% by weight or more, 95% by weight or more, or 96% by weight or more. By increasing the amount of heptyl acrylate used, its use effect (for example, the improvement of tanδ at -20°C of the adhesive and the improvement of impact resistance) can be effectively exerted. On the other hand, the upper limit of the proportion of heptyl acrylate in the monomer component is 100% by weight, which can be 99% by weight or less, or 98% by weight or less. From the perspective of copolymerizing carboxyl-containing monomers and other monomers, in some embodiments, the proportion of heptyl acrylate in the monomer component is less than 97% by weight. In some preferred embodiments, the proportion of heptyl acrylate in the monomer component is 96% by weight or less, which can be 95% by weight or less, or 94% by weight or less. Limiting the proportion of heptyl acrylate within the above range is preferred from the viewpoint of increasing the storage modulus, and is further advantageous from the viewpoint of increasing the repulsion resistance.

[0055] The acrylic polymer may be copolymerized with an alkyl (meth)acrylate other than heptyl acrylate (hereinafter also referred to as "optional alkyl (meth)acrylate"). As the optional alkyl (meth)acrylate, for example, a compound represented by the following formula (1) can be preferably used.

[0056] CH2=C(R 1 )COOR 2 (1)

[0057] Here, R in the above formula (1) 1 is a hydrogen atom or a methyl group. 2 is a chain alkyl group having 1 to 20 carbon atoms (wherein R 1 is a hydrogen atom, except for n-heptyl).

[0058] Examples of the optional alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl methacrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like. These optional alkyl (meth)acrylates may be used alone or in combination of two or more.

[0059] In some embodiments, the proportion of heptyl acrylate in the total amount of (meth) alkyl acrylate contained in the above-mentioned monomer component is, for example, 50% by weight or more (specifically, 50% to 100% by weight, for example, greater than 50% by weight), preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, particularly preferably 95% by weight or more, 99% by weight or more, or 100% by weight. By adopting such a monomer composition, the use effect of heptyl acrylate can be effectively exerted. According to the technology disclosed herein, it is not dependent on optional (meth) alkyl acrylates such as 2EHA and BA. Based on the effect of heptyl acrylate, it is possible to take into account both resilience resistance and impact resistance. Therefore, the technology disclosed herein can preferably be implemented in a manner in which the monomer component is substantially free of optional (meth) alkyl acrylate.

[0060] It should be noted that, in the present specification, the monomer component substantially not containing monomer A (such as the optional (meth)acrylate alkyl ester mentioned above) means that the monomer A is at least not used intentionally, and unintentional inclusion of the monomer A, for example, about 0.01 wt % or less, is allowed.

[0061] In some embodiments, the monomer component may include an alkyl (meth)acrylate having an alkyl group derived from biomass at the ester end (hereinafter also referred to as "biomass (meth)acrylate alkyl ester".). In recent years, environmental issues such as global warming have gradually received attention, and it is expected to reduce the use of fossil resource materials such as petroleum. In such a case, it is also required to reduce the use of fossil resource materials in the field of adhesives. By using biomass (meth)acrylate alkyl ester, an acrylic adhesive that takes into account the suppression of dependence on fossil resource materials can be appropriately realized.

[0062] Biomass (meth) alkyl acrylate is not particularly limited, for example, an ester of an alkanol from biomass and (meth) acrylic acid from biomass or not from biomass. Examples of alkanols from biomass include biomass ethanol, alkanols from plant raw materials such as palm oil or palm kernel oil, coconut oil, castor oil, etc. In the case where the carbon number of the alkanol from biomass is more than 3, the alkanol can be a straight chain or a branched chain. In some embodiments, as a biomass (meth) alkyl acrylate used in the synthesis of acrylic polymers, an ester of an alkanol from biomass and (meth) acrylic acid not from biomass can be used. In the biomass (meth) alkyl acrylate, the more carbon atoms of the alkanol, the higher the proportion of the number of carbons from biomass in the total number of carbons contained in the biomass (meth) alkyl acrylate, that is, the biomass carbon ratio of the (meth) alkyl acrylate. Therefore, in the above-mentioned biomass (meth) alkyl acrylate, from the perspective of reducing the dependence on fossil resource materials, it is desirable that the carbon number of the alkyl from biomass is more. On the other hand, when the carbon number of the alkyl group constituting the alkyl (meth)acrylate is too large, it tends to be difficult to obtain adhesive properties such as adhesive strength, and it may also be disadvantageous from the perspective of productivity such as synthesis, operability, and cost. In the method of using an ester of an alkanol derived from biomass and (meth)acrylic acid not derived from biomass as the biomass alkyl (meth)acrylate, it is desirable to use a material that balances adhesive properties with reduced dependence on fossil resource materials (more specifically, the biomass carbon ratio of the above-mentioned alkyl (meth)acrylate).

[0063] In some preferred embodiments, as heptyl acrylate, heptyl acrylate from biomass (biomass heptyl acrylate) is used. By using biomass heptyl acrylate, the effect of the technology disclosed herein can be achieved while reducing the dependence on fossil resource materials. The above-mentioned biomass heptyl ester is an ester of an alkanol from biomass and an acrylic acid from biomass or not from biomass, for example, an ester of an alkanol from biomass and an acrylic acid not from biomass can be used. In this compound, only the heptyl group comes from biomass. As heptyl acrylate from biomass, it is preferred to use n-heptyl acrylate from biomass (biomass n-heptyl acrylate).

[0064] The proportion of the biomass (meth) alkyl acrylate (preferably biomass heptyl acrylate) in the monomer component of the acrylic polymer is, for example, 50% by weight or more (e.g., greater than 50% by weight) in some embodiments, preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 85% by weight or more, particularly preferably 90% by weight or more, and may be 92% by weight or more, 94% by weight or more, or 96% by weight or more. In addition, the proportion of the biomass (meth) alkyl acrylate (preferably biomass heptyl acrylate) in the monomer component is less than 97% by weight, and in some embodiments, may be 95% by weight or less, 93% by weight or less, or 91% by weight or less.

[0065] In addition, the monomer component of the acrylic polymer preferably contains a carboxyl group-containing monomer. The carboxyl group-containing monomer can improve the cohesive force based on its polarity. In addition, when a cross-linking agent such as an isocyanate or epoxy cross-linking agent is used, the carboxyl group can become a cross-linking point of the acrylic polymer. By using a carboxyl group-containing monomer, the 65°C storage modulus of the adhesive can be increased, and an adhesive with excellent resilience to continuous load in the Z-axis direction can be easily obtained. In addition, by using a carboxyl group-containing monomer, for example, a more excellent adhesive property can be exerted on adherends such as highly polar materials.

[0066] As carboxyl-containing monomers, for example, ethylenically unsaturated monocarboxylic acids such as acrylic acid (AA), methacrylic acid (MAA), carboxylethyl (meth)acrylate, carboxylpentyl (meth)acrylate, crotonic acid, isocrotonic acid, etc.; ethylenically unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and citraconic acid. In addition, the carboxyl-containing monomer may be a monomer of a metal salt (such as an alkali metal salt) having a carboxyl group. The carboxyl-containing monomer may be used alone or in combination of two or more. Among them, AA and MAA may be listed as preferred carboxyl-containing monomers. AA is particularly preferred. When one or more carboxyl-containing monomers are used, the proportion of AA in the above-mentioned carboxyl-containing monomer is preferably 50% by weight or more, more preferably 70% by weight or more, and further preferably 90% by weight or more. In a particularly preferred embodiment, the carboxyl-containing monomer substantially only contains AA. Based on the polarity of the carboxyl group, its role as a crosslinking point, Tg (106°C) and other complex effects, AA is considered to be the most suitable monomer material among the carboxyl group-containing monomers disclosed herein in terms of balancing impact resistance and resilience against continuous load in the Z-axis direction.

[0067] The proportion of the carboxyl-containing monomer in the monomer component of the acrylic polymer is not particularly limited, and may be 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, or 2% by weight or more. In some preferred embodiments, the proportion of the carboxyl-containing monomer in the above-mentioned monomer component is greater than 3% by weight (specifically greater than 3.0% by weight), preferably greater than 4.0% by weight, more preferably greater than 4.5% by weight, further preferably greater than 5.0% by weight (for example, greater than 5.0% by weight), particularly preferably greater than 5.5% by weight, and may be greater than 6.0% by weight. By increasing the amount of carboxyl-containing monomer used, the cohesive force of the adhesive layer is improved based on the effect of the carboxyl-containing monomer, so that the 65°C storage modulus of the adhesive can be improved, and an adhesive with excellent resilience resistance can be easily obtained. In addition, it is appropriate that the amount of the carboxyl-containing monomer is, for example, less than 20% by weight of the total monomer component, preferably less than 15% by weight, and more preferably less than 12% by weight. In some preferred embodiments, the amount of the above-mentioned carboxyl-containing monomer may be less than 10% by weight, may be less than 8% by weight, may be less than 6% by weight, or may be less than 5% by weight. By reducing the amount of the carboxyl group-containing monomer (such as AA) used, tan δ at -20° C. tends to increase. By appropriately adjusting the amount of the carboxyl group-containing monomer used within the above range, an adhesive having both repulsion resistance and impact resistance can be easily obtained.

[0068] The acrylic polymer may be copolymerized with a functional group-containing monomer other than the carboxyl group-containing monomer (optional functional group-containing monomer). Examples of the optional functional group-containing monomers that can introduce a functional group that can become a crosslinking group into the acrylic polymer or contribute to the improvement of the adhesive strength include hydroxyl (OH group)-containing monomers (hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polypropylene glycol mono(meth)acrylate, etc.), acid anhydride group-containing monomers, amide group-containing monomers ((meth)acrylamide, N,N-dimethyl (meth)acrylamide, etc.), amino group-containing monomers (aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, etc.), epoxy group-containing monomers, cyano group-containing monomers, ketone group-containing monomers, monomers having a nitrogen atom-containing ring (N-vinyl-2-pyrrolidone, N-(meth)acryloylmorpholine, etc.), alkoxysilyl group-containing monomers, and imide group-containing monomers. The above optional functional group-containing monomers may be used alone or in combination of two or more.

[0069] In the case where the monomer components constituting acrylic polymers include the above-mentioned optional monomers containing functional groups, the content of the optional monomers containing functional groups in the monomer components is not particularly limited. From the perspective of appropriately exerting the effect brought by the use of optional monomers containing functional groups, the content of the optional monomers containing functional groups in the monomer components can be, for example, more than 0.1% by weight, more than 0.5% by weight is appropriate, and can be more than 1% by weight. In addition, for example, in the mode in which the monomer components of acrylic polymers contain heptyl acrylate and carboxyl-containing monomers, from the perspective of easily obtaining a balance of adhesive properties in the relationship with these monomer components, the content of the optional monomers containing functional groups in the monomer components is appropriate to be less than 40% by weight, preferably less than 20% by weight, and can also be less than 10% by weight (for example, less than 5% by weight). In some ways, the content of the optional monomers containing functional groups in the monomer components is, for example, less than 3% by weight, can be less than 1% by weight, can be less than 0.5% by weight, can be less than 0.3% by weight, and can also be less than 0.1% by weight. The technology disclosed herein can preferably be implemented in a mode in which the monomer components of acrylic polymers do not substantially include optional monomers containing functional groups.

[0070] In addition, as the above-mentioned optional functional group-containing monomer, a hydroxyl-containing monomer can be used. In this case, it is appropriate that the content of the hydroxyl-containing monomer is about 10% by weight or less (e.g., 0.001% by weight to 10% by weight) in the total monomer components, preferably about 5% by weight or less, and more preferably about 2% by weight or less. In some embodiments, the content of the hydroxyl-containing monomer in the monomer component can be, for example, less than 1% by weight, less than 0.5% by weight, less than 0.3% by weight, less than 0.1% by weight, or less than 0.01% by weight. The monomer component of the acrylic polymer may not substantially contain a hydroxyl-containing monomer. In the technology disclosed herein, by limiting the amount of hydroxyl-containing monomer used or not using a hydroxyl-containing monomer, it is possible to take into account the specified 65°C storage modulus G' and -20°C tanδ, and it is possible to satisfactorily achieve a high level of both resilience resistance and impact resistance.

[0071] Consider from the viewpoint of effectively bringing into play the effect that makes carboxyl-containing monomer copolymerization, carboxyl-containing monomer is used as the copolymerization component of acrylic acid-based polymer and the shared ratio in the functional group-containing monomer whole (comprising the functional group-containing monomer whole of carboxyl-containing monomer) is suitable for more than 30 weight %, is preferably more than 50 weight %, is more preferably more than 70 weight %, is further preferably more than 80 weight %, is particularly preferably more than 90 weight %, for example can be more than 95 weight %, can be more than 97 weight %, can be more than 98 weight %, can be more than 99 weight % (for example more than 99.9 weight %).The upper limit of the shared ratio of carboxyl-containing monomer in the above-mentioned functional group-containing monomer whole is 100 weight %, for example can be below 95 weight %.

[0072] For the purpose of improving cohesion, the monomer components constituting the acrylic polymer may also contain other copolymer components in addition to the above-mentioned functional group-containing monomers. Examples of other copolymer components include: vinyl ester monomers such as vinyl acetate; aromatic vinyl compounds such as styrene; (meth)acrylic acid cycloalkyl esters such as cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylic acid aryl esters (such as phenyl (meth)acrylate), (meth)acrylic acid aryloxyalkyl esters (such as phenoxyethyl (meth)acrylate), and (meth)acrylic acid arylalkyl esters (such as benzyl (meth)acrylate) containing aromatic rings; olefin monomers; chlorine-containing monomers; isocyanate-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate; alkoxy-containing monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; etc. The above-mentioned other copolymer components can be used alone or in combination of two or more.

[0073] The amount of the other copolymer components can be appropriately selected according to the purpose and use, without particular limitation, and from the viewpoint of appropriately exerting the effect brought by its use, it is appropriate to be more than 0.05 weight %, and it can be more than 0.5 weight %. In addition, from the viewpoint of easily obtaining the balance of adhesive performance, it is appropriate that the content of the other copolymer components in the monomer component is less than 20 weight %, and from the viewpoint of appropriately exerting the adhesive properties based on the indispensable monomer component, it is preferably less than 10 weight %, more preferably less than 8 weight %, and further preferably less than 5 weight %, for example, it can be less than 3 weight %, and it can also be less than 1 weight %. The technology disclosed herein can be preferably implemented in a manner that the monomer component does not substantially contain other copolymer components.

[0074] As other monomer components, the acrylic polymer may include a polyfunctional monomer having at least two (meth)acryloyl groups, vinyl groups, and other polymerizable functional groups (typically free radical polymerizable functional groups) having unsaturated double bonds. By using a polyfunctional monomer as a monomer component, the cohesive force of the adhesive layer can be improved. The polyfunctional monomer can be used as a cross-linking agent. There are no particular restrictions on the polyfunctional monomer, and examples thereof include: 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, neopentyl glycol di(meth)acrylate, and the like. The polyfunctional monomer can be used alone or in combination of two or more.

[0075] The usage amount of multifunctional monomers is not particularly limited, and can be appropriately set in a manner to achieve the purpose of use of the multifunctional monomers. The usage amount of multifunctional monomers can be less than about 3 wt % of the above-mentioned monomer components, preferably less than about 2 wt %, more preferably less than about 1 wt % (for example, less than about 0.5 wt %). The lower limit of the usage amount in the case of using multifunctional monomers is not particularly limited as long as it is greater than 0 wt %. Usually, by making the usage amount of multifunctional monomers be more than about 0.001 wt % (for example, more than about 0.01 wt %) of monomer components, the use effect of the multifunctional monomers can be appropriately exerted.

[0076] In a particularly preferred embodiment, as an acrylic polymer, the following acrylic polymer is used: an acrylic polymer synthesized using a monomer component substantially consisting of heptyl acrylate (preferably n-heptyl acrylate) and a carboxyl-containing monomer (preferably acrylic acid). According to the above-mentioned monomer composition, the effects of heptyl acrylate and the carboxyl-containing monomer can be effectively exerted, taking into account the prescribed 65°C storage modulus G' and -20°C tanδ, and it is possible to satisfactorily achieve a high level of both resilience resistance and impact resistance. From such a viewpoint, it is appropriate that the total proportion of heptyl acrylate and the carboxyl-containing monomer in the above-mentioned monomer component is 90% by weight or more (90% by weight to 100% by weight), preferably 95% by weight or more, more preferably 99% by weight or more, further preferably greater than 99.5% by weight, particularly preferably greater than 99.9% by weight (for example, greater than 99.99% by weight), and the total proportion of heptyl acrylate and the carboxyl-containing monomer in the above-mentioned monomer component can be 100% by weight.

[0077] The biomass carbon ratio of the monomer components constituting the acrylic polymer (the biomass carbon ratio of the acrylic polymer) can be, for example, 1% or more, 10% or more is appropriate, preferably 30% or more, more preferably 50% or more (for example, greater than 50%), 70% or more, 80% or more, or 90% to 100%. By designing in this way, an acrylic adhesive can be obtained that takes into account the suppression of dependence on fossil resource materials.

[0078] The method for obtaining the acrylic polymer is not particularly limited, and various polymerization methods known as the synthesis methods of acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization, can be appropriately adopted. For example, solution polymerization can be preferably adopted. As a monomer supply method when performing solution polymerization, a one-time feeding method of supplying all monomer raw materials at one time, a continuous supply (drip) method, a batch supply (drip) method, etc. can be appropriately adopted. The polymerization temperature can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be, for example, about 20°C to about 170°C (typically about 40°C to about 140°C).

[0079] The solvent (polymerization solvent) used for solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any one solvent or a mixed solvent of two or more selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (for example, monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone, etc. can be used.

[0080] The initiator used for the polymerization can be appropriately selected from the polymerization initiators known in the past according to the type of polymerization method. For example, one or more of the azo polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN) can be preferably used. As other examples of polymerization initiators, there can be listed: persulfates such as potassium persulfate; peroxide initiators such as benzoyl peroxide (BPO) and hydrogen peroxide; substituted ethane initiators such as phenyl substituted ethane; aromatic carbonyl compounds; etc. As other examples of polymerization initiators, redox initiators based on the combination of peroxides and reducing agents can be listed. Such polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used can be the usual amount, for example, it can be selected from the range of about 0.005 parts by weight to about 1 part by weight (typically about 0.01 parts by weight to about 1 part by weight) relative to 100 parts by weight of the total monomer components.

[0081] The weight average molecular weight (Mw) of the acrylic polymer is not particularly limited, and an acrylic polymer having an appropriate Mw that satisfies the above-mentioned storage modulus at 65°C and tanδ at -20°C can be used. In some embodiments, the Mw of the acrylic polymer may be greater than 600,000, greater than 650,000, 700,000 or more is appropriate, and may be 750,000 or more. The larger the Mw of the acrylic polymer, the easier it is to obtain an adhesive showing good cohesive force, and there is a tendency to improve resilience resistance. In some preferred embodiments, the Mw of the acrylic polymer is 800,000 or more, 850,000 or more, 900,000 or more, more preferably 1,000,000 or more (for example, greater than 1,000,000), further preferably 1,200,000 or more, particularly preferably 1,400,000 or more, 1,500,000 or more, or 1,600,000 or more. According to the monomer composition containing heptyl acrylate, it is easy to keep the viscosity low, so the synthesis of high molecular weight polymers is good, and it is easy to obtain acrylic polymers with the above-mentioned Mw. In addition, by using an acrylic polymer containing heptyl acrylate as a monomer unit and having a Mw of a specified value or more, the above-mentioned viscoelastic properties (specifically, 65°C storage modulus G' and -20°C tanδ) can be easily satisfied by the flexibility based on the chemical structure of the polymer and the cohesive force based on the molecular weight, and it is possible to satisfactorily achieve both high levels of resilience resistance and impact resistance. On the other hand, from the perspectives of impact resistance, adhesive strength, ease of synthesis, etc., it is appropriate that the Mw of the acrylic polymer is generally about 3 million or less, preferably 2.5 million or less, more preferably 2 million or less, further preferably 1.8 million or less, and can be 1.5 million or less, or 1.3 million or less. In some preferred embodiments, the Mw of the acrylic polymer can be 1.1 million or less, 1 million or less, 950,000 or less, or 900,000 or less.

[0082] The Mw of the acrylic polymer can be measured by gel permeation chromatography (GPC) and obtained as a standard polystyrene conversion value. Specifically, it can be measured under the following conditions using a trade name "HLC-8220GPC" (manufactured by Tosoh Corporation) as a GPC measuring device. The same is true in the examples described below.

[0083] [GPC measurement conditions]

[0084] Sample concentration: 0.2 wt% (tetrahydrofuran solution)

[0085] Sample injection volume: 10 μL

[0086] Eluent: Tetrahydrofuran (THF)

[0087] Flow rate: 0.6 mL / min

[0088] Column temperature (measurement temperature): 40°C

[0089] column:

[0090] Sample column: 1 TSKguardcolumn SuperHZ-H + 2 TSKgel SuperHZM-H (manufactured by Tosoh Corporation)

[0091] Reference column: 1 piece, trade name "TSKgel SuperH-RC" (manufactured by Tosoh Corporation)

[0092] Detector: Differential Refractometer (RI)

[0093] Standard sample: polystyrene

[0094] (Tackifying resin)

[0095] In some preferred embodiments, the adhesive layer includes a tackifying resin. By using a tackifying resin, a high adhesive force can be obtained. According to the technology disclosed herein, in a composition including a tackifying resin, the adhesive layer has a specified viscoelastic property (specifically, 65°C storage modulus G' and -20°C tanδ), and can exert excellent resilience resistance in the Z-axis direction. In particular, the effect of using a tackifying resin can be effectively exerted in a composition containing a high molecular weight acrylic polymer. As a tackifying resin, there is no particular restriction, for example, various tackifying resins such as rosin tackifying resins, terpene tackifying resins, hydrocarbon tackifying resins, epoxy tackifying resins, polyamide tackifying resins, elastomer tackifying resins, phenol tackifying resins, ketone tackifying resins, etc. can be used. Such tackifying resins can be used alone or in combination of two or more.

[0096] Specific examples of rosin-based tackifying resins include: unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins obtained by modifying these unmodified rosins by hydrogenation, disproportionation, polymerization, etc. (hydrogenated rosin, disproportionated rosin, polymerized rosin, other chemically modified rosins, etc. The same applies hereinafter); various other rosin derivatives; etc. Examples of the above-mentioned rosin derivatives include: rosin esters such as those obtained by esterifying unmodified rosin with alcohols (i.e., esterified rosin), and those obtained by esterifying modified rosin with alcohols (i.e., esterified rosin); unsaturated fatty acid-modified rosins obtained by modifying unmodified rosin and modified rosin with unsaturated fatty acids; unsaturated fatty acid-modified rosin esters obtained by modifying rosin esters with unsaturated fatty acids; rosin alcohols obtained by reducing the carboxyl groups in unmodified rosin, modified rosin, unsaturated fatty acid-modified rosin, or unsaturated fatty acid-modified rosin esters; metal salts of rosins (particularly rosin esters) such as unmodified rosin, modified rosin, and various rosin derivatives; rosin phenol resins obtained by adding phenol to rosins (unmodified rosin, modified rosin, various rosin derivatives, etc.) using an acid catalyst and thermally polymerizing them; etc. Among them, rosin esters are preferred.

[0097] Specific examples of rosin esters include esters of unmodified rosin or modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.), such as methyl ester, triethylene glycol ester, glycerol ester, pentaerythritol ester, etc., but are not particularly limited.

[0098] Examples of terpene tackifier resins include terpene resins such as α-pinene polymers, β-pinene polymers, and pine oil polymers; modified terpene resins obtained by modifying these terpene resins (phenol modification, aromatic modification, hydrogenation modification, hydrocarbon modification, etc.); etc. As an example of the above-mentioned modified terpene resin, terpene phenol resin can be cited.

[0099] Terpene-phenol resin refers to a polymer containing terpene residues and phenol residues, and is a concept that includes copolymers of terpenes and phenolic compounds (terpene-phenol copolymer resins) and resins obtained by phenol-modifying homopolymers or copolymers of terpenes (phenol-modified terpene resins). Specific examples of terpenes constituting such terpene-phenol resins include monoterpenes such as α-pinene, β-pinene, and limonene (including d-form, l-form, and d / l-form (pine oil).) Hydrogenated terpene-phenol resin refers to a hydrogenated terpene-phenol resin having a structure obtained by hydrogenating such a terpene-phenol resin. It is sometimes also called a hydrogenated terpene-phenol resin.

[0100] Examples of hydrocarbon tackifying resins include aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, aliphatic / aromatic copolymer (C5 / C9) petroleum resins, their hydrogenated products (for example, alicyclic petroleum resins obtained by hydrogenating aromatic petroleum resins), their various modified products (for example, maleic anhydride modified products), coumarone resins, coumarone indene resins and other hydrocarbon resins.

[0101] In some ways, as tackifying resin, at least one selected from rosin tackifying resin and terpene tackifying resin is preferably used. By making acrylic adhesive contain rosin tackifying resin and / or terpene tackifying resin, it is easy to obtain excellent anti-resilience in the Z-axis direction, in addition, it is possible to improve adhesive force. In some preferred ways, the total proportion of rosin tackifying resin and terpene tackifying resin in the tackifying resin whole contained in the adhesive layer can be, for example, greater than about 50% by weight (greater than 50% by weight and less than or equal to 100% by weight), can be about 70% by weight or more, can be about 80% by weight or more, can be about 90% by weight or more, can be 95% by weight or more, and can also be 99% by weight or more.

[0102] As some preferred modes, the above-mentioned tackifying resin includes one or more terpene-phenol resins. The technology disclosed herein can be preferably implemented in a mode in which about 25% by weight or more (more preferably about 30% by weight or more) of the total amount of the tackifying resin is a terpene-phenol resin. The proportion of the terpene-phenol resin in the total amount of the tackifying resin can be about 50% by weight or more, about 70% by weight or more, about 80% by weight or more, or about 90% by weight or more. It can be that substantially all (e.g., about 95% by weight or more and 100% by weight or less, further about 99% by weight or more and 100% by weight or less) of the tackifying resin is a terpene-phenol resin.

[0103] The content of the terpene-phenol resin in the adhesive layer is not particularly limited as long as the target viscoelastic properties are met. In some ways, from the viewpoint of improving adhesive force, relative to 100 parts by weight of acrylic polymer, the content of the terpene-phenol resin is generally about 1 part by weight or more, about 5 parts by weight or more is appropriate, preferably about 8 parts by weight or more, more preferably 10 parts by weight or more, and further preferably about 12 parts by weight or more (for example, 15 parts by weight or more). In addition, in some ways, relative to 100 parts by weight of acrylic polymer, the content of the terpene-phenol resin in the adhesive layer is, for example, less than 70 parts by weight, less than 60 parts by weight, or less than 50 parts by weight. In some preferred ways, from the viewpoint of resistance to rebound resilience, the content of the above-mentioned terpene-phenol resin is less than 40 parts by weight, more preferably less than 30 parts by weight, further preferably less than 25 parts by weight, particularly preferably less than 20 parts by weight, and less than 18 parts by weight.

[0104] Although not particularly limited, in some ways, the above-mentioned tackifying resin may include a tackifying resin (such as a terpene phenol resin) having a hydroxyl value greater than 20mgKOH / g. The hydroxyl value of the tackifying resin may be more than 30mgKOH / g. Wherein, a tackifying resin having a hydroxyl value of more than 50mgKOH / g is preferably used. Hereinafter, a tackifying resin having a hydroxyl value of more than 50mgKOH / g is sometimes referred to as a "high hydroxyl value resin". According to the tackifying resin comprising such a high hydroxyl value resin, in addition to adhesive force, by interacting with cross-linking agents such as isocyanate cross-linking agents, an adhesive layer with high cohesive force can also be achieved. In some ways, the above-mentioned tackifying resin may include a high hydroxyl value resin having a hydroxyl value of more than 60mgKOH / g (more preferably more than 70mgKOH / g). In addition, the above-mentioned high hydroxyl value resin (such as a terpene phenol resin) is preferably used in combination with an acrylic polymer containing heptyl acrylate as a monomer component, and can exert good adhesive force to the adherend and resist rebound to the continuous load in the Z-axis direction.

[0105] The upper limit of the hydroxyl value of the high hydroxyl value resin is not particularly limited. From the viewpoint of compatibility with acrylic polymers, the hydroxyl value of the high hydroxyl value resin is generally about 300 mgKOH / g or less, about 200 mgKOH / g or less is appropriate, preferably about 180 mgKOH / g or less, more preferably about 160 mgKOH / g or less, and further preferably about 140 mgKOH / g or less, which can be less than 120 mgKOH / g (e.g., 110 mgKOH / g or less). The technology disclosed herein can preferably be implemented in a manner that the tackifying resin includes a high hydroxyl value resin (e.g., a terpene tackifying resin, preferably a terpene phenol resin) having a hydroxyl value of 50 mgKOH / g to 200 mgKOH / g. In some embodiments, a high hydroxyl value resin having a hydroxyl value of 60 mgKOH / g to 140 mgKOH / g (e.g., 70 mgKOH / g to 110 mgKOH / g) can be preferably used.

[0106] Here, as the value of the hydroxyl value, there can be adopted a value measured by a potentiometric titration method specified in JIS K0070: 1992. The specific measurement method is as follows.

[0107] [Method for measuring hydroxyl value]

[0108] 1. Reagents

[0109] (1) As the acetylating agent, an acetylating agent obtained by taking about 12.5 g (about 11.8 mL) of acetic anhydride, adding pyridine thereto to make the total amount 50 mL, and stirring thoroughly was used. Alternatively, an acetylating agent obtained by taking about 25 g (about 23.5 mL) of acetic anhydride, adding pyridine thereto to make the total amount 100 mL, and stirring thoroughly was used.

[0110] (2) As a measurement reagent, a 0.5 mol / L potassium hydroxide ethanol solution was used.

[0111] (3) Separately, prepare toluene, pyridine, ethanol, and distilled water.

[0112] 2. Operation

[0113] (1) Accurately weigh about 2 g of a sample in a flat-bottom flask, add 5 mL of an acetylation reagent and 10 mL of pyridine, and install an air cooling tube.

[0114] (2) The flask was heated in a bath at 100°C for 70 minutes, then cooled naturally, 35 mL of toluene as a solvent was added from the top of the cooling tube and stirred, and then 1 mL of distilled water was added and stirred to decompose acetic anhydride. In order to complete the decomposition, the flask was heated in the bath again for 10 minutes and cooled naturally.

[0115] (3) The cooling tube was washed with 5 mL of ethanol and removed. Then, 50 mL of pyridine was added as a solvent and stirred.

[0116] (4) Use a volute pipette to add 25 mL of 0.5 mol / L potassium hydroxide ethanol solution.

[0117] (5) Potentiometric titration was performed using a 0.5 mol / L potassium hydroxide ethanol solution. The inflection point of the obtained titration curve was taken as the end point.

[0118] (6) In a blank test, the above (1) to (5) are carried out without adding a sample.

[0119] 3. Calculation

[0120] The hydroxyl value was calculated according to the following formula.

[0121] Hydroxyl value (mgKOH / g) = [(BC) × f × 28.05] / S + D

[0122] Here,

[0123] B: The amount of 0.5 mol / L potassium hydroxide ethanol solution used in the blank test (mL),

[0124] C: The amount of 0.5 mol / L potassium hydroxide ethanol solution used in the sample (mL),

[0125] f: Factor of 0.5 mol / L potassium hydroxide ethanol solution,

[0126] S: weight of the sample (g),

[0127] D: acid value,

[0128] 28.05: 1 / 2 of the molecular weight of potassium hydroxide, 56.11.

[0129] As the high hydroxyl value resin, a tackifier resin having a hydroxyl value of more than a specified value among the above-mentioned various tackifier resins can be used. One high hydroxyl value resin can be used alone or in combination of two or more. For example, as the high hydroxyl value resin, a terpene phenol resin having a hydroxyl value of more than 50 mgKOH / g can be preferably used. The terpene phenol resin can arbitrarily control the hydroxyl value according to the copolymerization ratio of phenol, so it is suitable.

[0130] Although there is no particular restriction, in the case of using a high hydroxyl value resin, the proportion of the high hydroxyl value resin (e.g., terpene phenol resin) in the overall tackifying resin contained in the adhesive layer can be about 5% by weight or more, 10% by weight or more, 15% by weight or more, or 20% by weight or more. In some embodiments, the proportion of the high hydroxyl value resin in the overall tackifying resin is, for example, preferably about 30% by weight or more. Thus, the effect of the use of high hydroxyl value resins can be satisfactorily exerted, and the adhesive force and the resilience to the continuous load in the Z-axis direction can be improved while having impact resistance. In some preferred embodiments, the proportion of the high hydroxyl value resin in the overall tackifying resin is about 40% by weight or more, about 50% by weight or more (e.g., greater than 50% by weight), about 60% by weight or more, about 70% by weight or more, about 80% by weight or more, or about 90% by weight or more. It can be that substantially all of the tackifying resin (e.g., about 95% by weight to about 100% by weight, and then about 99% by weight to about 100% by weight) is a high hydroxyl value resin.

[0131] The softening point of the above-mentioned high hydroxyl value resin is not particularly limited. The softening point of the high hydroxyl value resin can be, for example, above about 50°C. From the viewpoint of improving cohesion, a high hydroxyl value resin having a softening point (softening temperature) of above about 80°C can be preferably used. For example, a terpene phenol resin having such a softening point can be preferably used. The softening point of the high hydroxyl value resin can be above about 100°C, or above about 110°C. In some preferred embodiments, the softening point of the high hydroxyl value resin is above about 120°C, can be above about 130°C, or can be above about 135°C (further above about 140°C). There is no particular restriction on the upper limit of the softening point of the high hydroxyl value resin. From the viewpoint of adhesion to the adherend, a high hydroxyl value resin having a softening point of about 200°C or less (more preferably about 180°C or less) can be preferably used. In some embodiments, the softening point of the high hydroxyl value resin can be less than 160°C. In some preferred embodiments, as the high hydroxyl value resin, a high hydroxyl value resin having a softening point of less than 150° C. is used. By using a high hydroxyl value resin having a softening point of less than 150° C., an adhesive having both rebound resistance and impact resistance and excellent adhesive strength can be obtained. The softening point of the high hydroxyl value resin may be 145° C. or less.

[0132] It should be noted that the softening point of the tackifying resin in this specification is defined as the value measured according to the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is quickly melted at the lowest possible temperature and filled into a ring placed on a flat metal plate, taking care not to generate bubbles. After cooling, the raised portion is cut off from the plane containing the upper end of the ring with a slightly heated knife. Next, a support (ring stand) is placed in a glass container (heating bath) having a diameter of more than 85 mm and a height of more than 127 mm, and glycerin is injected until the depth reaches more than 90 mm. Next, a steel ball (diameter 9.5 mm, weight 3.5 g) and a ring filled with the sample are immersed in glycerin in a non-contact manner, and the temperature of the glycerin is maintained at 20°C ± 5°C for 15 minutes. Next, a steel ball is placed in the center of the sample surface in the ring and is placed in a fixed position on the support. Next, keep the distance from the upper end of the ring to the glycerin surface at 50 mm, place a thermometer so that the center of the mercury ball of the thermometer is at the same height as the center of the ring, and heat the container. Use the flame of the Bunsen burner used for heating to be located between the center and the edge of the bottom of the container to make the heating uniform. It should be noted that the rate of increase in the bath temperature after reaching 40°C after the start of heating must be 5.0°C ± 0.5°C per minute. The sample gradually softens and flows down from the ring. The temperature when it finally contacts the bottom plate is read and used as the softening point. The softening point is measured twice or more at the same time, and the average value is used.

[0133] The content of the high hydroxyl value resin in the adhesive layer is not particularly limited as long as it meets the viscoelastic properties as the target. In some ways, from the viewpoint of improving adhesive force, relative to 100 weight parts of acrylic polymers, the content of the high hydroxyl value resin is generally about 1 weight part or more, and it is appropriate to be about 5 weight parts or more, preferably about 8 weight parts or more, more preferably 10 weight parts or more, and further preferably about 12 weight parts or more (for example, 15 weight parts or more). In addition, in some ways, relative to 100 weight parts of acrylic polymers, the content of the high hydroxyl value resin in the adhesive layer is, for example, less than 70 weight parts, can be less than 60 weight parts, and can also be less than 50 weight parts. In some preferred embodiments, from the viewpoint of anti-rebound resilience, the content of the above-mentioned high hydroxyl value resin is less than 40 weight parts, more preferably less than 30 weight parts, further preferably less than 25 weight parts, particularly preferably less than 20 weight parts, and can be less than 18 weight parts.

[0134] Although there is no particular limitation, in some embodiments, the tackifying resin may include a tackifying resin having a hydroxyl value of less than 50 mgKOH / g. Hereinafter, a tackifying resin having a hydroxyl value of less than 50 mgKOH / g is sometimes referred to as a "low hydroxyl value resin". Although there is no particular limitation, it is preferred to use a low hydroxyl value resin in combination with a high hydroxyl value resin. The hydroxyl value of the low hydroxyl value resin may be less than 40 mgKOH / g. The lower limit of the hydroxyl value of the low hydroxyl value resin is 0 mgKOH / g or more, may be about 10 mgKOH / g or more, or may be about 15 mgKOH / g or more. As a low hydroxyl value resin, one appropriately selected from the tackifying resins having a hydroxyl value of less than 50 mgKOH / g in the tackifying resins exemplified above may be used alone or two or more may be used in combination. In some embodiments, the low hydroxyl value resin preferably includes a rosin-based tackifying resin. The low hydroxyl value resin may include one rosin-based tackifying resin alone, or may include two or more rosin-based tackifying resins in combination.

[0135] In some embodiments, the proportion of the rosin-based tackifying resin in the low-hydroxyl value resin as a whole may be, for example, greater than about 50% by weight, about 65% by weight or more, about 75% by weight or more, 85% by weight or more, or 95% by weight or more. The technology disclosed herein may preferably be implemented in a manner where substantially all (e.g., about 97% by weight or more, or 99% by weight or more, or 100% by weight) of the low-hydroxyl value resin is a rosin-based tackifying resin.

[0136] There is no particular restriction on the softening point of the above-mentioned low hydroxyl value resin. From the viewpoint of improving cohesion, it is preferred to use a low hydroxyl value resin having a softening point (softening temperature) of about 80°C or more. For example, a rosin-based tackifying resin having such a softening point can be preferably used. The softening point of the low hydroxyl value resin can be above about 100°C, can be above about 110°C, or can be above about 120°C. There is no particular restriction on the upper limit of the softening point of the low hydroxyl value resin. From the viewpoint of adhesion to the adherend, it is preferred to use a low hydroxyl value resin having a softening point of about 200°C or less (more preferably about 180°C or less). In some embodiments, the softening point of the low hydroxyl value resin can be below about 160°C, can be below about 150°C (for example, less than 150°C), can be below about 140°C, or can be below 130°C.

[0137] In some embodiments, as the tackifying resin, a tackifying resin T having a softening point of less than 150° C. is used. L By using tackifying resin T L , can obtain higher adhesive force to various adherends. L The softening point of the tackifying resin T may be below 145°C. L The lower limit of the softening point is not particularly limited. In some embodiments, from the perspective of exerting appropriate cohesive force, the tackifying resin TL The softening point of the tackifying resin may be, for example, above about 50°C, preferably above about 80°C, more preferably above about 100°C, and further preferably above about 110°C. In some preferred embodiments, the softening point of the tackifying resin is above about 120°C, above 130°C, or above 135°C (further above about 140°C).

[0138] As tackifying resin T L , one tackifier resin having a softening point of less than 150° C. selected from the above-mentioned tackifier resins may be used alone or in combination of two or more. L Preferably, it contains terpene phenol resin. L The terpene-phenol resin may be contained alone or in combination of two or more terpene-phenol resins.

[0139] In some embodiments, the terpene phenol resin is used in the tackifying resin T L The proportion of the total weight can be, for example, greater than about 50% by weight, about 65% by weight or more, about 75% by weight or more, about 85% by weight or more, or about 95% by weight or more. The technology disclosed herein can preferably be based on the tackifying resin T L The method is implemented in which substantially all (for example, about 97% by weight or more, or 99% by weight or more, or 100% by weight) of the terpene-phenol resin is used.

[0140] In addition, as a tackifying resin T L For example, it may or may not contain a tackifier resin having a softening point of less than 50°C, more preferably less than about 40°C (typically a tackifier resin of rosin, terpene, hydrocarbon, etc., such as hydrogenated rosin methyl ester, etc.). The tackifier resin showing such a low softening point may be a liquid tackifier resin that is liquid at 30°C. The liquid tackifier resin may be used alone or in combination of two or more. From the viewpoint of cohesion, etc., the content of the liquid tackifier resin may be tackifier resin T L The total amount is about 30% by weight or less, and appropriately about 10% by weight or less (eg, 0% to 10% by weight), and may be about 2% by weight or less (0.5% to 2% by weight), or may be less than 1% by weight.

[0141] Tackifying resin T L The content of is not particularly limited, but in some embodiments, it is appropriately about 70 parts by weight or less relative to 100 parts by weight of the acrylic polymer. L The amount of the tackifier resin T is limited to a prescribed amount or less, and the tackifier resin T has good rebound resistance and adhesive strength, and can improve the impact resistance. In some preferred embodiments, from the perspective of impact resistance, the tackifier resin T is 100 parts by weight of the acrylic polymer.L The usage amount of 60 parts by weight or less is appropriate, preferably 50 parts by weight or less, more preferably 40 parts by weight or less, can be 30 parts by weight or less, can be 25 parts by weight or less, can be 20 parts by weight or less, can be 18 parts by weight or less. In addition, in some embodiments, from the viewpoint of improving the adhesive force, the tackifier resin T is used in an amount of 100 parts by weight of the acrylic polymer. L The usage amount is, for example, 1 part by weight or more, 5 parts by weight or more is appropriate, preferably 8 parts by weight or more, more preferably 10 parts by weight or more, further preferably 12 parts by weight or more, and can be 15 parts by weight or more. The acrylic polymer containing heptyl acrylate as a monomer unit used in the technology disclosed herein has good compatibility with the tackifier resin, so by containing an appropriate amount of the tackifier resin, the desired characteristics can be achieved.

[0142] In some embodiments, the adhesive layer may contain a tackifying resin T L and a tackifying resin T having a softening point of 150°C or higher (e.g., 150°C to 200°C) H As a tackifying resin T H Among the tackifier resins exemplified above and having a softening point of 150° C. or higher, one type may be used alone or two or more types may be used in combination.

[0143] In some embodiments, the tackifying resin T L Preferably, the tackifier resin accounts for more than 50% by weight of the total amount of the tackifier resin contained in the adhesive layer. L By more effectively utilizing the tackifying resin T L Considering the effect of use, the tackifying resin T L The total amount of the tackifier resin contained in the adhesive layer is preferably 60% by weight or more, more preferably 70% by weight or more, further preferably 80% by weight or more, particularly preferably 90% by weight or more, 95% by weight or more, or 98% by weight or more. In some preferred embodiments, the tackifier resin contained in the adhesive layer substantially only comprises tackifier resin T L In this method, the tackifying resin T L The ratio of the total amount of the tackifier resin contained in the adhesive layer is in the range of 99% by weight to 100% by weight.

[0144] There is no particular restriction on the softening point of the tackifier resin. From the viewpoint of improving cohesive force, it is preferred to use a tackifier resin having a softening point (softening temperature) of about 80°C or more. For example, a terpene tackifier resin (terpene phenol resin, etc.) having such a softening point can be preferably used. The softening point of the tackifier resin can be above about 100°C, or above about 110°C. In some preferred embodiments, the softening point of the tackifier resin is above about 120°C, can be above about 130°C, or can be above about 135°C (further about 140°C or more). Among them, it is preferred to use a terpene phenol resin having the above-mentioned softening point. There is no particular restriction on the upper limit of the softening point of the tackifier resin. From the viewpoint of adhesion to the adherend, it is preferred to use a tackifier resin having a softening point of about 200°C or less (more preferably about 180°C or less). In some embodiments, the softening point of the tackifier resin can be less than 160°C, or less than 150°C.

[0145] In the case where the adhesive layer disclosed herein includes a tackifying resin, as the tackifying resin, from the viewpoint of increasing the biomass carbon ratio of the adhesive layer, a tackifying resin from a plant (plant-based tackifying resin) can be preferably used. As examples of plant-based tackifying resins, for example, the above-mentioned rosin-based tackifying resins and terpene-based tackifying resins can be cited. Plant-based tackifying resins can be used alone or in combination of two or more. In the case where the adhesive layer disclosed herein includes a tackifying resin, the proportion of the plant-based tackifying resin in the total amount of the tackifying resin is preferably 30% by weight or more (e.g., 50% by weight or more, typically 80% by weight or more). In some embodiments, the proportion of the plant-based tackifying resin in the total amount of the tackifying resin is 90% by weight or more (e.g., 95% by weight or more, typically 99% to 100% by weight). The technology disclosed herein can preferably be implemented in a manner that does not substantially contain a tackifying resin other than the plant-based tackifying resin.

[0146] The content of the tackifying resin in the adhesive layer is not particularly limited as long as the target viscoelastic properties are met. In some ways, from the viewpoint of improving adhesive force, relative to 100 parts by weight of acrylic polymer, the content of the tackifying resin is generally about 1 part by weight or more, about 5 parts by weight or more is appropriate, preferably about 8 parts by weight or more, more preferably 10 parts by weight or more, and more preferably about 12 parts by weight or more (for example, 15 parts by weight or more). In addition, in some ways, relative to 100 parts by weight of acrylic polymer, the content of the tackifying resin in the adhesive layer is, for example, less than 70 parts by weight, less than 60 parts by weight, or less than 50 parts by weight. In some preferred embodiments, from the viewpoint of resistance to rebound resilience, the content of the above-mentioned tackifying resin is less than 40 parts by weight, more preferably less than 30 parts by weight, more preferably less than 25 parts by weight, particularly preferably less than 20 parts by weight, and less than 18 parts by weight. The acrylic polymer containing heptyl acrylate as a monomer unit used in the disclosed technology has good compatibility with the tackifying resin, so by including an appropriate amount of tackifying resin, the desired characteristics can be achieved.

[0147] (Acrylic oligomer)

[0148] In some preferred embodiments, the adhesive layer contains an acrylic oligomer. By containing an acrylic oligomer, the adhesive force of the adhesive can be improved. According to the technology disclosed herein, in a composition containing an acrylic oligomer, the adhesive layer has a specified viscoelastic property (specifically, a 65°C storage modulus G' and -20°C tanδ), and can exert excellent resilience in the Z-axis direction. In particular, in a composition containing a high molecular weight acrylic polymer, the effect of using an acrylic oligomer can be effectively exerted.

[0149] The Tg of the acrylic oligomer is preferably about 0°C or more and about 300°C or less, preferably about 20°C or more and about 300°C or less, and more preferably about 40°C or more and about 300°C or less. By having Tg within the above range, the adhesive force can be appropriately improved. In some preferred embodiments, from the perspective of the cohesiveness of the adhesive, the Tg of the acrylic oligomer is about 30°C or more, more preferably about 50°C or more (for example, about 60°C or more), and from the perspective of adhesion, it is preferably about 200°C or less, more preferably about 150°C or less, and more preferably about 100°C or less (for example, about 80°C or less).

[0150] In this specification, the Tg of the acrylic oligomer refers to the Tg obtained by the Fox equation based on the composition of the above-mentioned monomer components. The Fox equation is shown below and is a relationship between the Tg of the copolymer and the glass transition temperature Tgi of the homopolymer obtained by homopolymerizing the monomers constituting the copolymer.

[0151] 1 / Tg=Σ(Wi / Tgi)

[0152] It should be noted that in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).

[0153] As the glass transition temperature of the homopolymer used in the calculation of Tg, the value recorded in the known materials can be used. For example, the value recorded in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. For monomers for which multiple values ​​are recorded in this document, the highest value is adopted.

[0154] For monomers whose homopolymer glass transition temperatures are not described in the above-mentioned documents, values ​​obtained by the following measurement method were used.

[0155] Specifically, 100 parts by weight of monomer, 0.2 parts by weight of 2,2'-azobisisobutyronitrile and 200 parts by weight of ethyl acetate as a polymerization solvent were added to a reactor having a thermometer, a stirrer, a nitrogen inlet tube and a reflux condenser, and stirred for 1 hour while circulating nitrogen. After removing oxygen from the polymerization system, the temperature was raised to 63°C and reacted for 10 hours. Then, it was cooled to room temperature to obtain a homopolymer solution with a solid content concentration of 33% by weight. Then, the homopolymer solution was cast on a release liner and dried to prepare a test sample (sheet-shaped homopolymer) with a thickness of about 2 mm. The test sample was punched into a disc with a diameter of 7.9 mm and clamped between parallel plates. The viscoelasticity was measured by a viscoelasticity testing machine (manufactured by TA Instruments Japan, model name "ARES") in a shear mode in a temperature range of -70°C to 150°C and at a heating rate of 5°C / min while applying a shear strain with a frequency of 1 Hz. The temperature equivalent to the peak temperature of tan δ was taken as the Tg of the homopolymer.

[0156] The weight average molecular weight (Mw) of acrylic oligomers can typically be greater than or equal to about 1000 and less than about 30000, preferably greater than or equal to about 1500 and less than about 20000, more preferably greater than or equal to about 2000 and less than about 10000. By making Mw in the above range, good adhesive force and resilience resistance can be obtained, so it is preferred. In some preferred modes, from the viewpoint of resilience resistance to the continuous load in the Z-axis direction, the Mw of acrylic oligomers is about 2500 or more (for example, about 3000 or more), in addition, from the viewpoint of adhesion, preferably about 7000 or less, more preferably about 5000 or less (for example, about 4500 or less, typically about 4000 or less). The Mw of acrylic oligomers can be measured by gel permeation chromatography (GPC), and the value converted as standard polystyrene is obtained. Specifically, the measurement was performed in a tetrahydrofuran solvent under the condition of a flow rate of about 0.5 mL / min using 2 TSK gel GMH-H (20) as columns in HPLC8020 manufactured by Tosoh Corporation.

[0157] Examples of the monomers constituting the acrylic oligomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, and (meth)acrylate. Alkyl (meth)acrylates such as isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate; esters of (meth)acrylic acid and alicyclic alcohols such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and tetrahydrodicyclopentadienyl (meth)acrylate ((meth)acrylates containing an alicyclic hydrocarbon group); aryl (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate; (meth)acrylates obtained from terpene compound derivative alcohols, etc. Such (meth)acrylates may be used alone or in combination of two or more.

[0158] As the acrylic oligomer, from the viewpoint of being able to further improve the adhesiveness of the adhesive layer, it is preferred to contain (meth) alkyl esters with a branched alkyl group such as isobutyl (meth) acrylate and tert-butyl (meth) acrylate; esters of (meth) acrylic acid and alicyclic alcohols such as cyclohexyl (meth) acrylate, isobornyl (meth) acrylate, and tetrahydrodicyclopentadienyl (meth) acrylate ((meth) acrylate) containing alicyclic hydrocarbon groups; and acrylic monomers with a relatively large structure represented by (meth) acrylates with a cyclic structure such as aryl (meth) acrylates such as phenyl (meth) acrylate and benzyl (meth) acrylate. In addition, when ultraviolet rays are used during the synthesis of the acrylic oligomer and the preparation of the adhesive layer, it is preferred to use substances with saturated bonds from the viewpoint of not causing polymerization inhibition. It is preferred to use (meth) alkyl esters with a branched alkyl group or esters with alicyclic alcohols ((meth) acrylate containing alicyclic hydrocarbon groups) as monomers constituting the acrylic oligomer. It should be noted that the branched alkyl (meth)acrylate, alicyclic (meth)acrylate, and aryl (meth)acrylate described above are equivalent to the (meth)acrylate monomer in the technology disclosed herein. The alicyclic hydrocarbon group may be a saturated or unsaturated alicyclic hydrocarbon group.

[0159] The proportion of (meth)acrylate monomers (e.g., alicyclic hydrocarbon group-containing (meth)acrylates) in all monomer components constituting the acrylic oligomer is typically greater than 50% by weight, preferably greater than 60% by weight, and more preferably greater than 70% by weight (e.g., greater than 80% by weight, and further greater than 90% by weight). In some preferred embodiments, the acrylic oligomer has a monomer composition that substantially only contains (meth)acrylate monomers.

[0160] As the constituent monomer components of acrylic oligomers, in addition to the above-mentioned (meth)acrylate monomers, functional group-containing monomers can also be used. Preferred examples of the above-mentioned functional group-containing monomers include: monomers having a nitrogen atom-containing ring (typically a nitrogen atom-containing heterocycle) such as N-vinyl-2-pyrrolidone and N-acryloylmorpholine; amino group-containing monomers such as (meth)acrylate N,N-dimethylaminoethyl; amide group-containing monomers such as N,N-diethyl (meth)acrylamide; carboxyl group-containing monomers such as AA and MAA; hydroxyl group-containing monomers such as (meth)acrylate 2-hydroxyethyl. These functional group-containing monomers can be used alone or in combination of two or more. Among them, carboxyl group-containing monomers are preferred, and AA is particularly preferred.

[0161] When all monomer components constituting the acrylic oligomer include functional group-containing monomers, the proportion of the functional group-containing monomers (e.g., carboxyl group-containing monomers such as AA) in the above-mentioned total monomer components is appropriately about 1% by weight or more, preferably 2% by weight or more, more preferably 3% by weight or more, and is appropriately about 15% by weight or less, preferably 10% by weight or less, more preferably 7% by weight or less.

[0162] Acrylic oligomers can be formed by polymerizing the monomer components that constitute them. The polymerization method and polymerization mode are not particularly limited, and various polymerization methods known in the past (such as solution polymerization, emulsion polymerization, bulk polymerization, photopolymerization, radiation polymerization, etc.) can be used in an appropriate manner. The types of polymerization initiators (such as azo polymerization initiators such as AIBN) that can be used as needed are basically as exemplified in the synthesis of acrylic polymers. Based on technical common sense, the amount of the polymerization initiator and the amount of the chain transfer agent such as n-dodecyl mercaptan that can be used are appropriately set to achieve the desired molecular weight, so detailed description is omitted here.

[0163] From the above viewpoints, preferred acrylic oligomers include, for example, homopolymers of tetrahydrodicyclopentadienyl methacrylate (DCPMA), cyclohexyl methacrylate (CHMA), isobornyl methacrylate (IBXMA), isobornyl acrylate (IBXA), tetrahydrodicyclopentadienyl acrylate (DCPA), 1-adamantyl methacrylate (ADMA), and 1-adamantyl acrylate (ADA). In addition, copolymers of CHMA and isobutyl methacrylate (IBMA), copolymers of CHMA and IBXMA, copolymers of CHMA and acryloylmorpholine (ACMO), copolymers of CHMA and diethylacrylamide (DEAA), copolymers of CHMA and AA, copolymers of ADA and methyl methacrylate (MMA), copolymers of DCPMA and IBXMA, and copolymers of DCPMA and MMA can be mentioned.

[0164] In the case of containing acrylic oligomer in the adhesive layer disclosed here, relative to 100 weight parts of acrylic polymers, its content is, for example, more than 0.1 weight part (for example, more than 1 weight part) is appropriate. From the viewpoint of better exerting the effect of acrylic oligomer, the content of above-mentioned acrylic oligomer is preferably more than about 5 weight parts, more preferably more than about 8 weight parts, further preferably more than about 10 weight parts, and particularly preferably more than about 12 weight parts. In addition, from the viewpoints such as compatibility with acrylic polymers, the content of above-mentioned acrylic oligomer is less than 50 weight parts (for example, less than 40 weight parts) relative to 100 weight parts of acrylic polymers is appropriate, preferably less than 30 weight parts, more preferably less than about 25 weight parts, and further preferably less than about 20 weight parts.

[0165] In some preferred embodiments, the adhesive layer comprises one or more of the above-mentioned tackifying resins and one or more of the acrylic oligomers. In the composition comprising an acrylic polymer containing heptyl acrylate as a monomer component, by using the tackifying resin and the acrylic oligomer together, it is possible to obtain excellent adhesion and at the same time, even in the use mode under harsh conditions such as strong rebound, it is possible to exert highly excellent resilience to continuous loads in the Z-axis direction. In particular, in the composition comprising a high molecular weight acrylic polymer, the effect of using the tackifying resin and the acrylic oligomer together can be effectively exerted. The content of the tackifying resin in the adhesive layer C T [Weight %] relative to the content of acrylic oligomer C O [weight %] ratio (C T / C O ) is not particularly limited. T / C O ) is, for example, appropriately greater than 0.1 and less than 9, preferably greater than 0.25 and less than 4, more preferably greater than 0.4 and less than 2, further preferably greater than 0.7 and less than 1.5, and can be greater than 0.8 and less than 1.2.

[0166] In some preferred embodiments, from the viewpoint of satisfactorily exerting the effects of the technology disclosed herein, the combined amount (total amount) of the tackifier resin and the acrylic oligomer contained in the adhesive layer is appropriately about 1 part by weight or more, preferably about 10 parts by weight or more, more preferably about 16 parts by weight or more, further preferably 20 parts by weight or more, and particularly preferably 25 parts by weight or more, relative to 100 parts by weight of the acrylic polymer. In addition, it is appropriately less than 120 parts by weight (for example, about 80 parts by weight or less), preferably less than 60 parts by weight, more preferably about 50 parts by weight or less, and further preferably about 40 parts by weight or less.

[0167] In the technology disclosed herein, the total amount (total amount) of the acrylic polymer, tackifying resin and acrylic oligomer in the adhesive layer is appropriately set in a manner that exerts the effect of the technology disclosed herein, and is not limited to a specific range. In some preferred modes, from the viewpoint of satisfactorily exerting the effect of the technology disclosed herein, it is appropriate that the total amount (total amount) of the acrylic polymer, tackifying resin and acrylic oligomer contained in the adhesive layer is greater than 50% by weight, preferably about 70% by weight or more, more preferably about 90% by weight or more, further preferably 95% by weight or more (e.g., 95% by weight or more and 100% by weight or less or 95% by weight or more and less than 100% by weight), and can be 98% by weight or more.

[0168] (Crosslinking agent)

[0169] In the technology disclosed herein, the adhesive composition used in forming the adhesive layer may contain a crosslinking agent as needed. The type of the crosslinking agent is not particularly limited, and examples thereof include isocyanate crosslinking agents, epoxy crosslinking agents, Azoline crosslinking agent, aziridine crosslinking agent, melamine crosslinking agent, peroxide crosslinking agent, urea crosslinking agent, metal alkoxide crosslinking agent, metal chelate crosslinking agent, metal salt crosslinking agent, carbodiimide crosslinking agent, hydrazine crosslinking agent, amine crosslinking agent, silane coupling agent, etc. The crosslinking agent can be used alone or in combination of two or more. Among them, isocyanate crosslinking agent, epoxy crosslinking agent, Oxazoline crosslinking agent, aziridine crosslinking agent, melamine crosslinking agent, more preferably isocyanate crosslinking agent, epoxy crosslinking agent.By appropriately selecting and using the crosslinking agent, the adhesive layer can obtain cohesive force, thereby being able to satisfactorily achieve a balance between resilience resistance and impact resistance while improving resilience resistance.It should be noted that the adhesive layer in the technology disclosed herein can contain the above-mentioned crosslinking agent in the form after the crosslinking reaction, the form before the crosslinking reaction, the form partially subjected to the crosslinking reaction, the intermediate or composite form thereof, etc. The above-mentioned crosslinking agent is typically mainly contained in the adhesive layer in the form after the crosslinking reaction.

[0170] As the isocyanate crosslinking agent, polyfunctional isocyanate (a compound having an average of two or more isocyanate groups per molecule, including a compound having an isocyanurate structure) can be preferably used. The isocyanate crosslinking agent can be used alone or in combination of two or more.

[0171] Examples of the polyfunctional isocyanate include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates.

[0172] Specific examples of aliphatic polyisocyanates include: 1,2-ethylene diisocyanate; 1,2-butylene diisocyanate, 1,3-butylene diisocyanate, 1,4-butylene diisocyanate and other butylene diisocyanates; 1,2-hexylene diisocyanate, 1,3-hexylene diisocyanate, 1,4-hexylene diisocyanate, 1,5-hexylene diisocyanate, 1,6-hexylene diisocyanate, 2,5-hexylene diisocyanate and other hexylene diisocyanates; 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, lysine diisocyanate and the like.

[0173] Specific examples of alicyclic polyisocyanates include isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; cyclopentyl diisocyanates such as 1,2-cyclopentyl diisocyanate and 1,3-cyclopentyl diisocyanate; hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tetramethylxylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0174] Specific examples of aromatic polyisocyanates include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, 2-nitrobiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, Isocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, naphthylene 1,4-diisocyanate, naphthylene 1,5-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, xylylene-1,4-diisocyanate, xylylene-1,3-diisocyanate, etc.

[0175] As preferred polyfunctional isocyanates, polyfunctional isocyanates having an average of three or more isocyanate groups per molecule can be exemplified. The trifunctional or higher isocyanates can be polymers (typically dimers or trimers) of difunctional or trifunctional or higher isocyanates, derivatives (e.g., addition reaction products of polyols and two or more molecules of polyfunctional isocyanates), polymers, etc. For example, polyfunctional isocyanates such as dimers of diphenylmethane diisocyanate or trimers of diphenylmethane diisocyanate, isocyanurates of hexamethylene diisocyanate (trimer adducts of isocyanurate structures), reaction products of trimethylolpropane and toluene diisocyanate, reaction products of trimethylolpropane and hexamethylene diisocyanate, polymethylene polyphenyl isocyanates, polyether polyisocyanates, polyester polyisocyanates, etc. can be cited. Examples of commercially available products of the polyfunctional isocyanate include "DURANATE TPA-100" manufactured by Asahi Kasei Chemicals, "Coronate L" manufactured by Tosoh Corporation, "Coronate HL" manufactured by Tosoh Corporation, "Coronate HK" manufactured by Tosoh Corporation, "Coronate HX" manufactured by Tosoh Corporation, and "Coronate 2096" manufactured by Tosoh Corporation.

[0176] The technology disclosed herein can be preferably implemented in a mode using at least an isocyanate crosslinking agent as a crosslinking agent. By using an isocyanate crosslinking agent, it is possible to obtain satisfactory repulsion resistance to a continuous load in the Z-axis direction.

[0177] The amount of isocyanate crosslinking agent used is not particularly limited. For example, relative to 100 parts by weight of acrylic polymer, it can be about 0.1 parts by weight or more. From the viewpoint of taking into account cohesion and adhesion, the amount of isocyanate crosslinking agent used is generally preferably about 0.3 parts by weight or more (for example, 0.5 parts by weight or more) relative to 100 parts by weight of acrylic polymer. In some preferred embodiments, relative to 100 parts by weight of acrylic polymer, the amount of isocyanate crosslinking agent used is about 0.8 parts by weight or more, more preferably about 1.0 parts by weight or more, further preferably about 1.2 parts by weight or more, and can be about 1.5 parts by weight or more. In addition, relative to 100 parts by weight of acrylic polymer, it is appropriate that the amount of the above-mentioned isocyanate crosslinking agent used is 10 parts by weight or less, preferably less than 5 parts by weight, more preferably less than 4.0 parts by weight, further preferably less than 3.0 parts by weight, particularly preferably less than 2.5 parts by weight, and can also be less than 2.0 parts by weight (for example, less than 1.7 parts by weight). By limiting the amount of the isocyanate crosslinking agent used within a predetermined range, it is possible to achieve a satisfactory balance between repulsion resistance and impact resistance while obtaining repulsion resistance against a continuous load in the Z-axis direction based on the use of the isocyanate crosslinking agent.

[0178] As the epoxy crosslinking agent, a compound having two or more epoxy groups in one molecule can be used without particular limitation. An epoxy crosslinking agent having 3 to 5 epoxy groups in one molecule is preferred. The epoxy crosslinking agent can be used alone or in combination of two or more.

[0179] Specific examples of epoxy crosslinking agents are not particularly limited, and examples thereof include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, etc. Commercially available products of epoxy crosslinking agents include trade names "TETRAD-C" and "TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "EPICRON CR-5L" manufactured by DIC Corporation, trade name "DENACOL EX-512" manufactured by Nagase Chemte X Co., Ltd., and trade name "TEPIC-G" manufactured by Nissan Chemical Industries, Ltd.

[0180] There is no particular restriction on the amount of epoxy crosslinking agent used. For example, relative to 100 parts by weight of acrylic polymer, the amount of epoxy crosslinking agent used can be greater than 0 parts by weight and less than or equal to about 1 part by weight (typically about 0.001 parts by weight to about 1 part by weight). From the perspective of properly exerting the effect of improving cohesion, it is usually appropriate to use an amount of epoxy crosslinking agent of about 0.002 parts by weight or more relative to 100 parts by weight of acrylic polymer, preferably about 0.005 parts by weight or more, for example, about 0.01 parts by weight or more. In addition, from the perspective of improving the adhesion to the adherend, relative to 100 parts by weight of acrylic polymer, the amount of epoxy crosslinking agent used is about 0.5 parts by weight or less, preferably about 0.2 parts by weight or less, more preferably about 0.1 parts by weight or less (for example, less than 0.1 parts by weight), can be 0.07 parts by weight or less, and can also be 0.04 parts by weight or less. In addition, from the viewpoint of avoiding the reduction of impact resistance caused by excessive crosslinking, it is usually appropriate to use an epoxy crosslinking agent in an amount of about 0.03 parts by weight or less, preferably about 0.02 parts by weight or less, relative to 100 parts by weight of the acrylic polymer. By limiting the amount of epoxy crosslinking agent used within a specified range, it is easy to maintain sufficient adhesive strength, and it is also easy to obtain resistance to rebounding against a continuous load in the Z-axis direction.

[0181] In some preferred embodiments, as the crosslinking agent, an isocyanate crosslinking agent and at least one crosslinking agent having a crosslinking functional group of a different type from that of the isocyanate crosslinking agent are used in combination. According to the technology disclosed herein, by using a crosslinking agent other than an isocyanate crosslinking agent (i.e., a crosslinking agent having a crosslinking reactive group of a different type from that of an isocyanate crosslinking agent, hereinafter also referred to as a "non-isocyanate crosslinking agent") and an isocyanate crosslinking agent in combination, it is possible to appropriately balance resilience resistance and impact resistance.

[0182] The type of non-isocyanate crosslinking agent that can be used in combination with the isocyanate crosslinking agent is not particularly limited, and can be appropriately selected from the above crosslinking agents. The non-isocyanate crosslinking agent can be used alone or in combination of two or more. In some preferred embodiments, an epoxy crosslinking agent can be used as the non-isocyanate crosslinking agent. For example, by using an isocyanate crosslinking agent and an epoxy crosslinking agent in combination, the resilience and impact resistance to the continuous load in the Z-axis direction can be better taken into account.

[0183] The relationship between the content of the isocyanate crosslinking agent and the content of the non-isocyanate crosslinking agent (preferably the epoxy crosslinking agent) is not particularly limited, and is appropriately set so as to satisfy the above-mentioned storage modulus at 65°C and tanδ at -20°C. The content of the isocyanate crosslinking agent is, for example, more than 1 times the content of the non-isocyanate crosslinking agent (preferably the epoxy crosslinking agent), and is appropriately about 10 times or more, preferably about 50 times or more, more preferably about 80 times or more, further preferably about 100 times or more (for example, more than 100 times), and particularly preferably about 120 times or more (for example, about 140 times or more). In addition, from the viewpoint of appropriately exerting the effect obtained by using an isocyanate crosslinking agent in combination with a non-isocyanate crosslinking agent (preferably an epoxy crosslinking agent), the content of the isocyanate crosslinking agent is generally, for example, about 1000 times or less, about 500 times or less, preferably about 300 times or less, more preferably about 200 times or less, and further preferably about 180 times or less (for example, about 160 times or less) relative to the content of the non-isocyanate crosslinking agent (preferably an epoxy crosslinking agent).

[0184] The content of the crosslinking agent in the adhesive composition disclosed herein (the total amount of the crosslinking agent) is not particularly limited. From the viewpoint of cohesion, usually relative to 100 parts by weight of acrylic polymer, the content of the above-mentioned crosslinking agent is about 0.001 parts by weight or more, about 0.002 parts by weight or more is appropriate, preferably about 0.005 parts by weight or more, more preferably about 0.01 parts by weight or more, further preferably about 0.02 parts by weight or more, particularly preferably about 0.03 parts by weight or more. In some ways, relative to 100 parts by weight of acrylic polymer, the content of the crosslinking agent is about 0.1 parts by weight or more, more preferably about 0.5 parts by weight or more, further preferably about 1.0 parts by weight or more, can be about 1.2 parts by weight or more, can also be about 1.5 parts by weight or more. In addition, usually relative to 100 parts by weight of acrylic polymer, the content of the crosslinking agent in the adhesive composition is about 20 parts by weight or less, about 15 parts by weight or less is appropriate, preferably about 10 parts by weight or less (e.g., about 5 parts by weight or less). In some embodiments, the content of the crosslinking agent is 4.0 parts by weight or less, more preferably 3.0 parts by weight or less, and further preferably 2.5 parts by weight or less, and may be 2.0 parts by weight or less (e.g., less than 2.0 parts by weight), or 1.8 parts by weight or less, relative to 100 parts by weight of the acrylic polymer. By appropriately setting the total amount of the crosslinking agent used within the above range, both the rebound resistance and the impact resistance can be satisfactorily taken into account.

[0185] (Other additives)

[0186] In addition to the above-mentioned components, the adhesive composition may contain various additives commonly used in the field of adhesives, such as leveling agents, crosslinking aids, plasticizers, softeners, fillers, colorants (pigments, dyes, etc.), antistatic agents, anti-aging agents, ultraviolet absorbers, antioxidants, rust inhibitors, and light stabilizers, as needed. For such various additives, conventionally known substances can be used, which are not the characteristics of the present invention, so detailed description is omitted.

[0187] The adhesive layer (layer containing adhesive) disclosed herein can be an adhesive layer formed by an aqueous adhesive composition, a solvent-based adhesive composition, a hot melt adhesive composition, or an active energy ray-curable adhesive composition. An aqueous adhesive composition refers to an adhesive composition in the form of an adhesive (adhesive layer forming component) contained in a solvent (aqueous solvent) having water as the main component, typically an aqueous adhesive composition containing what is called a water-dispersible adhesive composition (a composition in the form of at least a portion of the adhesive dispersed in water). In addition, a solvent-based adhesive composition refers to an adhesive composition in the form of an adhesive contained in an organic solvent. As the organic solvent contained in the solvent-based adhesive composition, one or more of the organic solvents (toluene, ethyl acetate, etc.) that can be used in the above-mentioned solution polymerization can be used without particular limitation. The technology disclosed herein can be preferably implemented in a manner having an adhesive layer formed by a solvent-based adhesive composition from the viewpoint of adhesive properties, etc.

[0188] The adhesive layer disclosed herein can be formed by a method known in the past. For example, a method for forming an adhesive layer by applying an adhesive composition on a surface with peelability (peeling surface) or a non-peeling surface and drying it can be adopted. For the adhesive sheet with the structure of a substrate, for example, a method (direct method) can be adopted by directly applying (typically coating) an adhesive composition on the substrate and drying it to form an adhesive layer. In addition, it is also possible to adopt a method (transfer method) by applying an adhesive composition on a surface with peelability (peeling surface) and drying it to form an adhesive layer on the surface, and transferring the adhesive layer to the substrate. From the viewpoint of productivity, a transfer method is preferred. As the above-mentioned peeling surface, the surface of a peeling liner, the back side of the substrate that has been peeled off, etc. can be utilized. It should be noted that the adhesive layer disclosed herein is typically formed continuously, but is not limited to such a mode, for example, it can also be an adhesive layer formed into regular or irregular patterns such as dot-shaped and strip-shaped.

[0189] The adhesive composition can be applied using a conventionally known coater such as a gravure roll coater, a die coater, or a bar coater. Alternatively, the adhesive composition can be applied by dipping, curtain coating, or the like.

[0190] From the viewpoint of promoting the crosslinking reaction and improving the manufacturing efficiency, the drying of the adhesive composition is preferably carried out under heating. The drying temperature can be, for example, about 40°C to about 150°C, and is generally preferably about 60°C to about 130°C. After the adhesive composition is dried, it can be further aged for the purpose of regulating the migration of components in the adhesive layer, carrying out the crosslinking reaction, relaxing the strain that may exist in the adhesive layer, etc.

[0191] (thickness)

[0192] There is no particular restriction on the thickness of the adhesive layer, and a composition having an adhesive layer with an appropriate thickness in the range of, for example, 0.1 μm to 500 μm can be adopted according to the purpose of use, the purpose of use, etc. In some ways, from the viewpoint of avoiding the adhesive sheet being too thick, it is appropriate that the thickness of the adhesive layer is generally about 100 μm or less, preferably about 70 μm or less, more preferably about 60 μm or less, and further preferably about 50 μm or less. The thickness of the adhesive layer can be about 35 μm or less, for example, about 30 μm or less. The adhesive layer with limited thickness can well meet the requirements of thickness thinning and lightweight. In addition, usually, when the thickness of the adhesive layer becomes smaller, it has a tendency to reduce impact resistance and adhesion to the adherend, but according to the technology disclosed herein, by having a composition of an adhesive layer with a limited thickness, sufficient impact resistance and adhesion can be achieved. From the viewpoint of adhesion to the adherend, in some ways, the lower limit of the thickness of the adhesive layer is about 0.5 μm or more, which is appropriate, can be about 1 μm or more, and is advantageous to be about 3 μm or more, preferably about 10 μm or more, more preferably about 12 μm or more (for example, greater than 12 μm), and further preferably about 15 μm or more, for example, about 18 μm or more. In some preferred ways, the thickness of the adhesive layer is greater than 20 μm, can be 24 μm or more, or can be 27 μm or more. The adhesive sheet disclosed herein can be an adhesive sheet having an adhesive layer of the above thickness on both sides of the substrate. In addition, in a double-sided adhesive sheet with a substrate having a first adhesive layer and a second adhesive layer on each side of the substrate, the first adhesive layer and the second adhesive layer can be the same thickness or different thicknesses from each other.

[0193] (Biomass Carbon Ratio)

[0194] In some embodiments, the adhesive layer includes a material from biomass, and its biomass carbon ratio can be above a specified value. The biomass carbon ratio of the adhesive layer is, for example, above 1%, above 10%, preferably above 30%, and more preferably above 50%. A high biomass carbon ratio of the adhesive indicates that the amount of fossil resource materials represented by petroleum is small. In this view, the higher the biomass carbon ratio of the adhesive, the more preferred. For example, the biomass carbon ratio of the adhesive layer can be above 55%, above 60%, above 70%, above 75%, above 80%, or greater than 80%. The upper limit of the biomass carbon ratio is defined as 100%, and can be below 99%. From the perspective of the availability of the material, it can be below 95%, or below 90%. From the perspective of easy to exert good adhesive properties, in some embodiments, the biomass carbon ratio of the adhesive layer can be, for example, below 90%, below 85%, or below 80%.

[0195] <Base Material>

[0196] In the form of the adhesive sheet disclosed herein as a single-sided adhesive or double-sided adhesive with a substrate, as the substrate supporting (lining) the adhesive layer, resin film, paper, cloth, rubber sheet, foam sheet, metal foil, their composites, etc. can be used. As examples of paper, Japanese paper, kraft paper, glassine, high-quality paper, synthetic paper, surface-coated paper, etc. can be cited. As examples of cloth, woven fabrics, non-woven fabrics, etc. obtained by spinning various fibrous materials alone or in a blended manner can be cited. As the above-mentioned fibrous materials, examples can be given: cotton, staple fiber, Manila hemp, pulp, rayon, acetate fiber, polyester fiber, polyvinyl alcohol fiber, polyamide fiber, polyolefin fiber, etc. As examples of rubber sheets, natural rubber sheets, butyl rubber sheets, etc. can be cited. As examples of foam sheets, foamed polyolefin sheets, foamed polyurethane sheets, foamed chloroprene rubber sheets, etc. can be cited. As examples of metal foil, aluminum foil, copper foil, etc. can be cited. It should be noted that the substrate supporting the adhesive layer is also referred to as a substrate layer in the adhesive sheet.

[0197] The substrate may be formed of a biomass-derived material or a non-biomass-derived material. From the viewpoint of producing a PSA sheet that reduces dependence on fossil resource materials, it is preferred to use a biomass-derived substrate material (typically a resin film).

[0198] In addition, the substrate can also be formed using recyclable materials, recycled materials (also referred to as regenerated materials). As the regenerated material, a resin film is preferably used. Since the resin film (for example, polyester films such as PET films) can be reused, whether or not materials from plants are used, continuous reproduction can be carried out by reusing the used resin film, and the environmental load can be reduced. Such reusable resin films and recycled resin films are also referred to as regenerated films. The above-mentioned regenerated materials (for example, regenerated films) can be formed from materials from biomass, and can also be formed from materials that are not from biomass.

[0199] As the substrate constituting the adhesive sheet with substrate, a substrate containing a resin film as a base film can be preferably used. The above-mentioned base film is typically a (non-dependent) member that can independently maintain a shape. The substrate in the technology disclosed herein can be substantially composed of such a base film. Alternatively, the above-mentioned substrate can also include an auxiliary layer in addition to the above-mentioned base film. As examples of the above-mentioned auxiliary layers, a colored layer, a reflective layer, a primer layer, an antistatic layer, etc. arranged on the surface of the above-mentioned base film can be cited.

[0200] The resin film is a film having a resin material as a main component (for example, a component with a content greater than 50% by weight in the resin film). Examples of resin films include: polyolefin resin films such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymers; polyester resin films such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN); vinyl chloride resin films; vinyl acetate resin films; polyimide resin films; polyamide resin films; fluorine-containing resin films; cellophane; etc. The resin film may be a rubber film such as a natural rubber film or a butyl rubber film. Among them, from the viewpoint of operability and processability, a polyester film is preferred, and a PET film is particularly preferred.

[0201] It should be noted that, in this specification, "resin film" is typically a non-porous sheet, which is a concept different from so-called non-woven fabrics and woven fabrics (in other words, a concept other than non-woven fabrics and woven fabrics). The above-mentioned resin film can be any one of a non-stretched film, a uniaxially stretched film, and a biaxially stretched film. In addition, such a resin film can be non-foamed. Here, a non-foamed resin film refers to a resin film that has not been intentionally treated to form a foam body. Specifically, a non-foamed resin film can be a resin film having a foaming ratio of less than 1.1 times (for example, less than 1.05 times, typically less than 1.01 times).

[0202] The above-mentioned base material (e.g., resin film) may be mixed with various additives such as fillers (inorganic fillers, organic fillers, etc.), colorants, dispersants (surfactants, etc.), anti-aging agents, antioxidants, ultraviolet absorbers, antistatic agents, lubricants, plasticizers, etc. as needed. The mixing ratio of various additives may be less than about 30% by weight (e.g., less than about 20% by weight, typically less than about 10% by weight).

[0203] The above-mentioned substrate (e.g., resin film) may be a single-layer structure, or may have a multilayer structure of two, three or more layers. From the viewpoint of shape stability, the substrate is preferably a single-layer structure. In the case of a multilayer structure, it is preferred that at least one layer (preferably all layers) is a layer having a continuous structure of the above-mentioned resin (e.g., polyester resin). The manufacturing method of the substrate (typically a resin film) may appropriately adopt a conventionally known method without particular limitation. For example, conventionally known film forming methods such as extrusion molding, inflation molding, T-die casting molding, and calendering roll molding may be appropriately adopted.

[0204] The surface of the substrate may be subjected to conventionally known surface treatments such as corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, and primer application. Such surface treatments may be used to improve the adhesion between the substrate and the adhesive layer, in other words, the anchoring property of the adhesive layer to the substrate.

[0205] In addition, when the technology disclosed herein is implemented in the form of a single-sided adhesive sheet with a substrate, a peeling treatment can be applied to the back of the substrate as needed. The peeling treatment can be, for example, a treatment in which a conventional silicone-based, long-chain alkyl-based, fluorine-containing type or other peeling agent is applied to a film-like shape of typically about 0.01 μm to about 1 μm (for example, 0.01 μm to 0.1 μm). By implementing this peeling treatment, an effect such as easy unwinding of a roll-shaped roll of the adhesive sheet can be obtained.

[0206] In the adhesive sheet of the method including substrate, the thickness of the substrate is not particularly limited. From the viewpoint of avoiding the adhesive sheet from becoming too thick, the thickness of the substrate can be, for example, about 200 μm or less, preferably about 150 μm or less, and more preferably about 100 μm or less. According to the purpose of use and the method of use of the adhesive sheet, the thickness of the substrate can be about 70 μm or less, or about 50 μm or less, or about 30 μm or less (for example, about 25 μm or less). In some ways, the thickness of the substrate can be about 20 μm or less, or about 15 μm or less, or about 10 μm or less (for example, about 5 μm or less). By reducing the thickness of the substrate, even if the total thickness of the adhesive sheet is the same, the thickness of the adhesive layer can be further increased. It is advantageous to consider from the viewpoint of improving the adhesion to the adherend and the substrate. The lower limit of the substrate is not particularly limited. From the viewpoint of the operability (handleability) and processability of the adhesive sheet, the thickness of the substrate is generally about 0.5 μm or more (e.g., 1 μm or more), preferably about 2 μm or more, for example, about 6 μm or more. In some embodiments, the thickness of the substrate can be about 15 μm or more, or about 25 μm or more.

[0207] <Foam Base Material>

[0208] In other embodiments, a foam substrate is used as a substrate. The foam substrate disclosed herein is a substrate having a portion having bubbles (bubble structure), typically a substrate comprising at least one layer of layered foam (foam layer). The foam substrate may be a substrate consisting of one or more layers of foam layers. The foam substrate may be, for example, a substrate consisting essentially of only one or more layers of foam layers. Without particular limitation, as a preferred example of the foam substrate in the technology disclosed herein, a foam substrate comprising a single layer (one layer) of foam layer may be cited.

[0209] The thickness of the foam substrate is not particularly limited and can be appropriately set according to the strength, flexibility, and purpose of use of the adhesive sheet. From the viewpoint of thinning, the thickness of the foam substrate is usually less than 1 mm, and 0.70 mm or less is appropriate, preferably less than 0.40 mm, and more preferably less than 0.30 mm. The technology disclosed herein can be preferably implemented in a manner that the thickness of the foam substrate is less than 0.25 mm (typically less than 0.18 mm, for example, less than 0.16 mm) from the viewpoints of processability, etc. In addition, from the viewpoints of the impact resistance of the adhesive sheet, the thickness of the foam substrate is usually more than 0.04 mm, more than 0.05 mm is appropriate, preferably more than 0.06 mm, and more preferably more than 0.07 mm (for example, more than 0.08 mm). The technology disclosed herein can be preferably implemented in a manner that the thickness of the foam substrate is more than 0.10 mm (typically greater than 0.10 mm, preferably more than 0.12 mm, for example, more than 0.13 mm). As the thickness of the foam substrate increases, the impact resistance tends to improve.

[0210] The density of the foam substrate (referred to as apparent density, which is the same unless otherwise specified) is not particularly limited, and may be, for example, 0.1 g / cm 3 ~0.9g / cm 3 From the perspective of impact resistance, the density of the foam substrate is 0.8 g / cm 3 The following is appropriate, preferably 0.7 g / cm 3 Below (e.g. 0.6 g / cm 3 In one embodiment, the density of the foam substrate may be less than 0.5 g / cm 3 , can also be less than 0.4g / cm 3 (e.g. 0.5 g / cm 3 In addition, from the viewpoint of impact resistance, the density of the foam substrate is preferably 0.12 g / cm 3 More preferably 0.15 g / cm 3 More preferably, 0.2 g / cm 3 Above (e.g. 0.3 g / cm 3 In one embodiment, the density of the foam substrate may be 0.4 g / cm 3 Above, it can also be 0.5g / cm 3 More than (for example, more than 0.5 g / cm 3 ), and further 0.55 g / cm 3 The density (apparent density) of the foam substrate can be measured in accordance with JIS K6767.

[0211] The average bubble diameter of the foam substrate is not particularly limited. From the viewpoint of stress dispersion, it is preferably 300 μm or less, more preferably 200 μm or less, and further preferably 150 μm or less. The lower limit of the average bubble diameter is not particularly limited. From the viewpoint of height difference followability, it is usually appropriate to be more than 10 μm, preferably more than 20 μm, more preferably more than 30 μm, and further preferably more than 40 μm (for example, more than 50 μm). In one embodiment, the average bubble diameter can be more than 55 μm, or more than 60 μm. It should be noted that the average bubble diameter referred to herein refers to the average bubble diameter converted to a positive sphere obtained by observing the cross section of the foam substrate using an electron microscope.

[0212] The cell structure of the foam of the foam substrate disclosed herein is not particularly limited. As the cell structure, it can be any of a continuous cell structure, an independent cell structure, and a semi-continuous semi-independent cell structure. From the viewpoint of impact absorption, an independent cell structure and a semi-continuous semi-independent cell structure are preferred.

[0213] 25% compression strength C of foam substrate 25 There are no particular restrictions, but for example, it may be 20 kPa or more (typically 30 kPa or more, and further 40 kPa or more). 25 Generally, 250 kPa or more is appropriate, preferably 300 kPa or more (for example, 400 kPa or more). The adhesive sheet having such a foam substrate can exhibit good durability against impacts caused by dropping, etc. For example, the adhesive sheet can be better prevented from being broken by impact. 25 The upper limit of C is not particularly limited, but is usually 1300 kPa or less (e.g., 1200 kPa or less). 25 It may be 1000 kPa or less, 800 kPa or less, further 600 kPa or less (e.g. 500 kPa or less), or 360 kPa or less. 25 It can be 20 kPa to 200 kPa (typically 30 kPa to 150 kPa, for example 40 kPa to 120 kPa). A PSA sheet having such a foam substrate can be a PSA sheet with excellent cushioning properties. For example, the foam substrate can absorb the impact of a drop, thereby better preventing the PSA sheet from peeling off.

[0214] 25% compression strength C of foam substrate 25It means: the foam substrate is cut into 30 mm squares and the obtained material is stacked to form a test sample with a thickness of about 2 mm, and the test sample is sandwiched between a pair of flat plates, and the load when it is compressed to a thickness equivalent to 25% of the initial thickness (load at a compression rate of 25%). That is, it refers to the load when the above-mentioned test sample is compressed to a thickness equivalent to 75% of the initial thickness. The above-mentioned compression strength is measured according to JISK6767. As a specific measurement procedure, the above-mentioned test sample is set in the central part of the above-mentioned pair of flat plates, and is continuously compressed to a specified compression rate by reducing the interval between the above-mentioned flat plates, and the flat plates are stopped here, and the load after 10 seconds is measured. The compression strength of the foam substrate can be controlled, for example, by the degree of crosslinking, density, size and shape of the bubbles of the material constituting the foam substrate.

[0215] There is no particular restriction on the tensile elongation of the foam substrate. For example, a foam substrate having a tensile elongation of 200% to 800% (more preferably 400% to 600%) in the longitudinal direction (MD) can be preferably used. In addition, a foam substrate having a tensile elongation of 50% to 800% (more preferably 200% to 500%) in the width direction (TD) is preferably used. The elongation of the foam substrate is measured according to JIS K6767. The elongation of the foam substrate can be controlled, for example, by the degree of crosslinking, the apparent density (foaming ratio), etc.

[0216] The tensile strength (tensile strength) of the foam substrate is not particularly limited. For example, a foam substrate having a tensile strength in the longitudinal direction (MD) of 5MPa to 35MPa (preferably 10MPa to 30MPa) can be preferably used. In addition, a foam substrate having a tensile strength in the width direction (TD) of 1MPa to 25MPa (more preferably 5MPa to 20MPa) is preferably used. The tensile strength of the foam substrate is measured according to JISK6767. The tensile strength of the foam substrate can be controlled, for example, by the degree of crosslinking, apparent density (foaming ratio), etc.

[0217] The material of the foam substrate is not particularly limited. Generally, it is preferred to use a foam substrate comprising a foam layer formed of a foam of a plastic material (plastic foam). The plastic material (including the meaning of rubber material) used to form the plastic foam is not particularly limited and can be appropriately selected from known plastic materials. One plastic material can be used alone or two or more plastic materials can be used in appropriate combination.

[0218] Specific examples of plastic foams include: polyolefin resin foams such as PE foams and PP foams; polyester resin foams such as PET foams, PEN foams, and PBT foams; polyvinyl chloride resin foams such as polyvinyl chloride foams; vinyl acetate resin foams; polyphenylene sulfide resin foams; amide resin foams such as aliphatic polyamide (nylon) resin foams and wholly aromatic polyamide (aramid) resin foams; polyimide resin foams; polyetheretherketone (PEEK) foams; styrene resin foams such as polystyrene foams; urethane resin foams such as polyurethane resin foams, etc. In addition, as plastic foams, rubber resin foams such as polychloroprene rubber foams can also be used.

[0219] As a preferred foam, a polyolefin resin foam (hereinafter also referred to as a "polyolefin foam") can be exemplified. As the plastic material constituting the polyolefin foam (i.e., the polyolefin resin), various known or commonly used polyolefin resins can be used without particular limitation. For example, PE such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE), PP, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, etc. can be cited. As an example of LLDPE, a Ziegler-Natta catalyst-based linear low-density polyethylene, a metallocene catalyst-based linear low-density polyethylene, etc. can be cited. Such polyolefin resins can be used alone or in appropriate combinations of two or more.

[0220] As preferred examples of the foam substrate in the technology disclosed herein, from the viewpoints of impact resistance, water resistance, dust resistance, etc., there can be listed polyolefin foam substrates such as PE foam substrates substantially composed of foams of PE resins and PP foam substrates substantially composed of foams of PP resins. Here, PE resins refer to resins with ethylene as the main monomer (i.e., the main component in the monomer), and in addition to HDPE, LDPE, LLDPE, etc., they can also include ethylene-propylene copolymers and ethylene-vinyl acetate copolymers with a copolymerization ratio of ethylene greater than 50% by weight. Similarly, PP resins refer to resins with propylene as the main monomer. As the foam substrate in the technology disclosed herein, PE foam substrates can be preferably used.

[0221] The manufacturing method of the above-mentioned plastic foam (typically a polyolefin foam) is not particularly limited, and various known methods can be appropriately adopted. For example, it can be manufactured by a method including a molding step, a cross-linking step and a foaming step of the above-mentioned plastic material or the above-mentioned plastic foam. In addition, a stretching step can be included as needed.

[0222] As a method for crosslinking the above-mentioned plastic foam, for example, a chemical crosslinking method using an organic peroxide or the like, or an ionizing radiation crosslinking method by irradiating ionizing radiation, etc., can be cited, and these methods can be used in combination. As the above-mentioned ionizing radiation, electron beams, α rays, β rays, γ rays, etc. can be exemplified. The dose of ionizing radiation is not particularly limited, and can be set to an appropriate irradiation dose in consideration of the target physical properties of the foam substrate (such as the degree of crosslinking), etc.

[0223] The foam substrate may contain various additives such as fillers (inorganic fillers, organic fillers, etc.), anti-aging agents, antioxidants, ultraviolet absorbers, antistatic agents, lubricants, plasticizers, flame retardants, surfactants, etc., as needed.

[0224] The foam substrate in the technology disclosed herein may be colored black, white, etc., in order to exhibit desired design and optical properties (e.g., light shielding, light reflectivity, etc.) in the adhesive sheet having the foam substrate. The coloring may be performed using one or more known organic or inorganic colorants alone or in appropriate combinations.

[0225] The surface of the foam substrate may be subjected to appropriate surface treatment as required. The surface treatment may be, for example, a chemical or physical treatment for improving the adhesion of an adjacent material (e.g., an adhesive layer). Examples of the surface treatment include corona discharge treatment, chromic acid treatment, ozone exposure, flame exposure, ultraviolet irradiation treatment, plasma treatment, and application of a primer (primer).

[0226] <Release liner>

[0227] In the technology disclosed herein, a release liner can be used when forming an adhesive layer, making an adhesive sheet, storing, circulating, shaping, etc. the adhesive sheet before use. As a release liner, there is no particular limitation, for example, a release liner having a release treatment layer on the surface of a liner substrate such as a resin film or paper; a release liner containing a fluorine-containing polymer (polytetrafluoroethylene, etc.), etc. can be used. The above-mentioned release treatment layer can be formed by surface treating the above-mentioned liner substrate with a release treatment agent such as silicone, long-chain alkyl, fluorine-containing, molybdenum sulfide, etc. As a liner substrate, as with the substrate of the aforementioned adhesive sheet, a substrate formed using a material from biomass, a recycled material (recycled film, etc.) can be preferably used.

[0228] <Total Thickness of Adhesive Sheet>

[0229] The total thickness of the adhesive sheet disclosed herein (including an adhesive layer and a substrate layer, but not including a release liner.) is not particularly limited. The total thickness of the adhesive sheet can be, for example, about 1 mm or less, about 500 μm or less, about 300 μm or less, and from the perspective of thinning, about 200 μm or less is appropriate, and can be about 150 μm or less (for example, about 100 μm or less). In some preferred embodiments, the thickness of the adhesive sheet can be about 50 μm or less, for example, about 35 μm or less. The lower limit of the thickness of the adhesive sheet is, for example, 0.1 μm or more (for example, 0.5 μm or more), about 3 μm or more is appropriate, preferably about 10 μm or more, more preferably about 15 μm or more, about 50 μm or more, and about 100 μm or more. An adhesive sheet having a thickness above a specified value is easy to obtain adhesion to an adherend, and in addition, has a tendency to be excellent in operability. It should be noted that in an adhesive sheet without a substrate, the thickness of the adhesive layer is the total thickness of the adhesive sheet.

[0230] <Characteristics of Adhesive Sheet>

[0231] In some embodiments, the 180-degree peel strength (adhesion to SUS) of the adhesive sheet to the stainless steel plate is preferably about 15N / 25mm or more (for example, 17N / 25mm or more). An adhesive sheet showing such an adhesive force to SUS can exert excellent adhesive force. The above-mentioned adhesive force to SUS is more preferably about 20N / 25mm or more, further preferably about 23N / 25mm or more, and particularly preferably 25N / 25mm or more (for example, 26N / 25mm or more). There is no particular restriction on the upper limit of the above-mentioned adhesive force to SUS. From the perspective of taking into account other adhesive properties such as resilience resistance, it can usually be, for example, about 50N / 25mm or less. The above-mentioned adhesive force to SUS is measured by using a SUS plate as an adherend under a measurement environment of 23°C and 50%RH, at a tensile speed of 300mm / minute and a peeling angle of 180 degrees. More specifically, it is measured by the method described in the embodiments described later.

[0232] In addition, the adhesive sheet disclosed herein preferably has a ridge height of less than 2.0 mm at the end of the test in a repulsion resistance evaluation test implemented by the following method. The adhesive sheet satisfying the above characteristics substantially has particularly excellent repulsion resistance to the peel load in the thickness direction (Z-axis direction) of the adhesive sheet only, and it is particularly difficult to peel off the continuous peel load in this direction. In addition, when the adhesive sheet attached to the adherend (such as a portable electronic device, a module as its component) is in a high temperature and high humidity condition during storage, it can also exert stable repulsion resistance. It is appropriate that the above-mentioned ridge height is less than 1.5 mm, preferably less than 1.0 mm, more preferably less than 0.7 mm, further preferably less than 0.5 mm, and particularly preferably less than 0.4 mm. It should be noted that the above-mentioned ridge height is the height of the thickness (30 μm in the embodiment described later) of the adhesive sheet.

[0233] [Resilience resistance evaluation test]

[0234] A polyethylene terephthalate (PET) film with a length of 70 mm, a width of 10 mm, and a thickness of 75 μm was fixed to the lower surface of a polycarbonate plate with a length of 30 mm, a width of 10 mm, and a thickness of 2 mm at one end of the length direction of the PET film. Next, the PET film was bent along the length direction, and the other end of the bent PET film in the length direction was fixed to the upper surface of the polycarbonate plate with an adhesive area of ​​3 mm × 10 mm using an adhesive sheet. This state was maintained under the conditions of 65°C, 90% RH, and 72 hours (resistance to rebound evaluation test). Then, the height [mm] of the bulge of the adhesive sheet from the polycarbonate plate after 72 hours (at the end of the test) was measured.

[0235] More specifically, the repulsion resistance evaluation test is performed by the method described in the repulsion resistance test in the Z-axis direction of the examples described later.

[0236] The PSA sheet disclosed herein preferably has an impact adhesive strength of 0.3 J / cm in an impact resistance test conducted in accordance with JIS K6855. 2 The adhesive sheet satisfying this characteristic can be a bonding means having excellent durability against impact in the shear direction. Therefore, for example, it can be preferably used as a component fixing unit in a portable electronic device that is expected to be exposed to impact caused by falling or collision. According to the technology disclosed herein, it is possible to provide a bonding means showing 0.35 J / cm 2 More than (more preferably 0.40 J / cm 2 More preferably, 0.45 J / cm 2 Above, particularly preferably 0.50 J / cm 2 The upper limit of the impact adhesive strength is not particularly limited, and can be, for example, 3.00 J / cm2 From the viewpoint of being able to easily achieve a balance between high resistance to repulsion and high resistance to impact, the impact strength may be, for example, 1.00 J / cm 2 Below, it can be 0.80J / cm 2 Below, it can also be 0.60J / cm 2 More specifically, the impact resistance test was carried out by the method described in the impact resistance test of the examples described later.

[0237] In some embodiments, the adhesive sheet includes a material from biomass, and its biomass carbon ratio can be above a specified value. The biomass carbon ratio of the adhesive sheet is, for example, 1% or more, 10% or more, preferably 30% or more, and more preferably 50% or more. The high biomass carbon ratio of the adhesive sheet indicates that the amount of fossil resource materials represented by petroleum is small. In this view, the higher the biomass carbon ratio of the adhesive sheet, the more preferred. For example, the biomass carbon ratio of the adhesive sheet can be 55% or more, 60% or more, 70% or more, 75% or more, 80% or more, or greater than 80%. The upper limit of the biomass carbon ratio is defined as 100%, and can be 99% or less. From the perspective of the availability of the material, it can be 95% or less, or 90% or less. From the perspective of easy to play a good adhesive performance, in some embodiments, the biomass carbon ratio of the adhesive sheet can be, for example, 90% or less, 85% or less, or 80% or less.

[0238] <Purpose>

[0239] The use of the adhesive sheet disclosed herein is not particularly limited and can be used for various purposes. The adhesive sheet disclosed herein can take into account both rebound resistance and impact resistance, and can therefore be suitable for gluing and fixing components in applications requiring high rebound resistance and impact resistance. For example, it can be satisfactorily used for fixing components in various portable devices (portable devices). Non-limiting examples of the portable electronic devices include: mobile phones, smart phones, tablet personal computers, notebook personal computers, various wearable devices (for example, wrist-worn devices such as watches, modular devices such as those worn on a part of the body with clips, straps, etc., eyewear devices such as glasses (monocular, binocular, and helmet-type), clothing devices such as those worn on shirts, socks, hats, etc. in the form of accessories, and ear-worn devices such as headphones), digital cameras, digital video cameras, audio devices (portable music players, voice recorders, etc.), calculators (desktop calculators, etc.), portable game devices, electronic dictionaries, electronic notepads, electronic books, in-vehicle information devices, portable radios, portable televisions, portable printers, portable scanners, portable modems, etc. It should be noted that in this specification, "portable" is not sufficient to be interpreted as merely portable, and it essentially has the level of portability that an individual (standard adult) can carry relatively easily.

[0240] The adhesive sheet disclosed herein (typically a double-sided adhesive sheet) can be used to fix the components of the portable electronic device as described above in the form of a bonding material processed into various shapes. Among them, it can be satisfactorily used in a portable electronic device with a liquid crystal display device. For example, in an electronic device (typically a portable electronic device such as a smart phone) having a display portion (which can be a display portion of a liquid crystal display device) such as a touch panel display, in a device in which an elastic member such as FPC is bent and stored in an internal space for its large screen, it is preferred to use the adhesive sheet disclosed herein in the purpose of fixing the elastic adherend. By using the adhesive sheet disclosed herein, the elastic adherend can be stably fixed in a bent state, and the fixed state can be continuously maintained. Thus, the above-mentioned elastic member stored in the limited internal space in the portable electronic device in a bent state is positioned with high precision by the adhesive sheet disclosed herein, and can be maintained in a stable fixed state. In addition, as a material configured inside the portable electronic device as described above, materials with polarity and rigidity such as polycarbonate and polyimide can be cited. For such a material (polar and rigid resin material), the adhesive sheet disclosed herein can satisfactorily exert the resilience to the continuous load in the Z-axis direction. Alternatively, the adhesive sheet disclosed herein is satisfactorily used for fixing the use of components such as protective glass having a three-dimensional shape (typically a curved surface shape) constituting the portable electronic device in a portable electronic device. In an adhesive sheet for fixing a component having such a three-dimensional surface shape, there is a tendency to apply a relatively large continuous load in the Z-axis direction. By using the adhesive sheet disclosed herein, even a component having a three-dimensional shape as described above can be stably fixed.

[0241] In recent years in particular, the development of electronic devices (typically portable electronic devices such as smart phones and tablet computers) having a display portion (which may be a display portion of a liquid crystal display device) such as the above-mentioned touch panel display is oriented towards both large screens and high functionality. With regard to large screens, a countermeasure has been taken to bend elastic components such as the above-mentioned FPC and store them in the internal space. On the other hand, with regard to high functionality, new functions such as pressure-sensitive sensors with higher precision pressure sensing performance and facial recognition unlocking functions have been realized. In order to achieve higher performance and higher quality products, the high integration of circuits such as FPCs that bear them is indispensable. As a highly integrated unit of the circuit, for example, a two-sided FPC or a multi-layer FPC can be listed, but the directionality of the rigidity of the FPC is increased. It is expected that the improvement of the resilience resistance to continuous loads in the Z-axis direction, such as the resilience resistance test in the Z-axis direction described later, will become a required characteristic. The preferred embodiment of the adhesive sheet of the technology disclosed herein can show excellent rebound resistance under harsh high temperature and high humidity conditions (strong rebound conditions) as in the rebound resistance test in the Z-axis direction described later, and can therefore be more suited for use in the above-mentioned next-generation touch panel display-equipped electronic devices (typically touch panel display-equipped portable electronic devices such as smartphones).

[0242] Although not particularly limited, in some embodiments, the adhesive sheet is preferably used in electronic devices including various light sources such as LEDs (light emitting diodes) and light-emitting elements such as self-luminous organic ELs. For example, it can be preferably used in electronic devices (typically portable electronic devices) having organic EL display devices and liquid crystal display devices.

[0243] Figure 4 Schematically shows an example of a portable electronic device (smartphone) using the adhesive sheet disclosed herein. Figure 4 As shown, a battery (heating element) 540 is built into the interior of the housing 520 of the portable electronic device 500. In addition, the portable electronic device 500 is configured to include an adhesive sheet 550. In this configuration example, the adhesive sheet 550 has the form of a double-sided adhesive sheet (double-sided adhesive sheet) for fixing the components constituting the portable electronic device 500. It should be noted that the portable electronic device 500 has a touch panel 570 that also functions as an input unit in the display portion. The adhesive sheet disclosed herein is preferably used as a constituent element (component bonding means) of the portable electronic device as described above.

[0244] In addition, the adhesive sheet disclosed herein may have an adhesive layer containing an acrylic polymer with a high biomass carbon ratio in some embodiments, and thus can be used as a substitute for conventional acrylic adhesives (i.e., acrylic adhesives with a low biomass carbon ratio) in various applications using the acrylic adhesive, thereby helping to reduce dependence on fossil resource materials. The adhesive sheet disclosed herein can be preferably used as an adhesive sheet with reduced dependence on fossil resource materials.

[0245] The matters disclosed in this specification include the following.

[0246] [1] A portable electronic device, wherein an adhesive sheet is bonded to a member constituting the electronic device, the adhesive sheet having an adhesive layer containing an acrylic polymer, the acrylic polymer being a polymer containing a monomer component of heptyl acrylate, the adhesive layer having a storage modulus G' at 65°C of 20,000 Pa or more and a tan δ at -20°C of 0.3 or more, wherein the tan δ refers to a ratio (G" / G') of a loss modulus G" of the adhesive layer to a storage modulus G'.

[0247] [2] The portable electronic device according to [1] above, wherein the acrylic polymer has a weight average molecular weight of 700,000 or more.

[0248] [3] A portable electronic device according to [1] or [2] above, wherein the glass transition temperature of the adhesive layer is in the range of -15°C to 15°C, wherein the glass transition temperature of the adhesive layer refers to the glass transition temperature obtained from the peak temperature of tanδ in a dynamic viscoelasticity measurement.

[0249] [4] The portable electronic device according to any one of [1] to [3] above, wherein the adhesive layer further contains a tackifier resin.

[0250] [5] The portable electronic device according to any one of [1] to [4] above, wherein the adhesive layer contains at least one selected from a rosin-based tackifier resin and a terpene-based tackifier resin.

[0251] [6] The portable electronic device according to any one of [1] to [5] above, wherein the content of the tackifier resin in the adhesive layer is 70 parts by weight or less relative to 100 parts by weight of the acrylic polymer.

[0252] [7] The portable electronic device according to any one of [1] to [6] above, wherein the pressure-sensitive adhesive layer further contains an acrylic oligomer.

[0253] [8] The portable electronic device according to any one of [1] to [7] above, wherein the adhesive composition used to form the adhesive layer contains at least one selected from an isocyanate crosslinking agent and an epoxy crosslinking agent.

[0254] [9] The portable electronic device according to any one of [1] to [8] above, wherein the pressure-sensitive adhesive sheet has a 180-degree peel strength with respect to a stainless steel plate of 20 N / 25 mm or more.

[0255]

[11] A pressure-sensitive adhesive sheet, comprising a pressure-sensitive adhesive layer comprising an acrylic polymer, wherein the acrylic polymer is a polymer containing a monomer component of heptyl acrylate, wherein the pressure-sensitive adhesive layer has a storage modulus G' at 65°C of 20,000 Pa or more and a tan δ at -20°C of 0.3 or more, wherein the tan δ refers to a ratio (G" / G') of a loss modulus G" of the pressure-sensitive adhesive layer to a storage modulus G'.

[0256]

[12] The pressure-sensitive adhesive sheet according to

[11] above, wherein the acrylic polymer has a weight average molecular weight of 700,000 or more.

[0257]

[13] The adhesive sheet according to

[11] or

[12] above, wherein the glass transition temperature of the adhesive layer is in the range of -15°C to 15°C, wherein the glass transition temperature of the adhesive layer refers to the glass transition temperature obtained from the peak temperature of tanδ in a dynamic viscoelasticity measurement.

[0258]

[14] The pressure-sensitive adhesive sheet according to any one of

[11] to

[13] above, wherein the pressure-sensitive adhesive layer further contains a tackifier resin.

[0259]

[15] The PSA sheet according to any one of

[11] to

[14] above, wherein the PSA layer comprises at least one selected from the group consisting of a rosin-based tackifier resin and a terpene-based tackifier resin.

[0260]

[16] The pressure-sensitive adhesive sheet according to any one of

[11] to

[15] above, wherein the content of the tackifier resin in the pressure-sensitive adhesive layer is 70 parts by weight or less relative to 100 parts by weight of the acrylic polymer.

[0261]

[17] The pressure-sensitive adhesive sheet according to any one of

[11] to

[16] above, wherein the pressure-sensitive adhesive layer further contains an acrylic oligomer.

[0262]

[18] The adhesive sheet according to any one of

[11] to

[17] above, wherein the adhesive composition used to form the adhesive layer contains at least one selected from an isocyanate crosslinking agent and an epoxy crosslinking agent.

[0263]

[19] The adhesive sheet according to any one of

[11] to

[18] above, wherein the adhesive sheet has a 180-degree peel strength with respect to a stainless steel plate of 20 N / 25 mm or more.

[0264]

[20] The pressure-sensitive adhesive sheet according to any one of

[11] to

[19] above, wherein the pressure-sensitive adhesive sheet is used for fixing components in a portable electronic device.

[0265]

[21] A portable electronic device comprising the pressure-sensitive adhesive sheet according to any one of

[11] to

[20] above.

[0266] Example

[0267] Hereinafter, some embodiments of the present invention will be described, but it is not intended to limit the present invention to the contents shown in these embodiments. It should be noted that, unless otherwise specified, in the following description, "parts" and "%" are weight references.

[0268] <Example 1>

[0269] (Synthesis of Acrylic Polymer)

[0270] In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet tube, a reflux condenser and a dropping funnel, 94 parts of n-heptyl acrylate (n-HpA) and 6 parts of acrylic acid (AA) as monomer components and ethyl acetate as a polymerization solvent were added, and stirred for 2 hours while introducing nitrogen. By doing so, the oxygen in the polymerization system was removed, and then 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and solution polymerization was carried out at 60°C to 70°C for 8 hours to obtain a solution of an acrylic polymer. The weight average molecular weight (Mw) of the acrylic polymer is 1.2 million. The adjustment of Mw is carried out by adjusting the concentration of the monomer components during polymerization. It should be noted that the above-mentioned n-HpA is a compound synthesized using heptol from biomass and having a heptyl group from biomass at the ester end.

[0271] (Preparation of Adhesive Composition)

[0272] To the acrylic polymer solution obtained above, 30 parts of terpene phenol A (trade name "YS POLYSTER T-115", a terpene phenol resin manufactured by Yasuhara Chemical Co., Ltd., softening point of about 115°C, hydroxyl value of 30 mgKOH / g to 60 mgKOH / g) as a tackifier resin, 3 parts of an isocyanate crosslinking agent (trade name "CORONATE L", a 75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Corporation) and 0.03 parts of an epoxy crosslinking agent (trade name "TETRAD-C", 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, manufactured by Mitsubishi Gas Chemical Co., Ltd.) were added (based on solid content) with respect to 100 parts of the acrylic polymer contained in the solution, and the mixture was stirred and mixed to prepare the adhesive composition of this example.

[0273] (Manufacturing of adhesive sheet)

[0274] The obtained adhesive composition was applied to the release surface of a polyester release film (trade name "Diafoil MRF", manufactured by Mitsubishi Chemical Corporation) with a thickness of 38 μm, and dried at 100°C for 2 minutes to form an adhesive layer with a thickness of 30 μm. The release surface of a polyester release film (trade name "Diafoil MRF", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) with a thickness of 25 μm was attached to the adhesive layer. By doing so, a substrate-free double-sided adhesive sheet with a thickness of 30 μm, both sides of which were protected by the above two polyester release films, was obtained.

[0275] <Example 2 to Example 6 and Comparative Example 1 to Comparative Example 4>

[0276] The adhesive compositions of each example were prepared by the same method as in Example 1 except that the monomer composition, Mw, type and amount of tackifier resin, amount of acrylic oligomer, and type and amount of crosslinking agent of acrylic polymer were changed as shown in Table 1. Using the obtained adhesive compositions, substrate-free double-sided adhesive sheets (thickness 30 μm) of each example were prepared in the same manner as in Example 1. The Mw of acrylic polymer was adjusted by adjusting the concentration of monomer components during polymerization.

[0277] It should be noted that in Table 1, 2EHA represents 2-ethylhexyl acrylate, BA represents n-butyl acrylate, 4HBA represents 4-hydroxybutyl acrylate, and HEA represents hydroxyethyl acrylate. In addition, terpene phenol B is a terpene phenol resin with a softening point of about 145° C. and a hydroxyl value of 70 mgKOH / g to 110 mgKOH / g manufactured by Yasuhara Chemical Co., Ltd., and rosin ester is a terpene phenol resin with a softening point of about 145° C. and a hydroxyl value of 32 mgKOH / g manufactured by Arakawa Chemical Industries, Ltd., under the trade name "PENSEL D125".

[0278] In addition, as an acrylic oligomer, an acrylic oligomer prepared by the following method was used. Specifically, 95 parts of cyclohexyl methacrylate (CHMA) and 5 parts of AA, 10 parts of AIBN as a polymerization initiator, and ethyl acetate as a polymerization solvent were added to a reaction container equipped with a stirrer, a thermometer, a nitrogen inlet tube, a reflux condenser, and a dropping funnel, and stirred for 1 hour in a nitrogen stream to remove oxygen in the polymerization system, and then the temperature was raised to 85° C. and reacted for 5 hours to obtain an acrylic oligomer with a solid content concentration of 50%. The Mw of the obtained acrylic oligomer was 3600.

[0279] <Evaluation method>

[0280] [Adhesion to SUS]

[0281] Under the measurement environment of 23°C and 50%RH, a PET film with a thickness of 50 μm was pasted on one adhesive surface of the adhesive sheet (double-sided adhesive sheet) for lining, and the film was cut into a size of 25 mm in width and 100 mm in length, thereby preparing a measurement sample. Under the environment of 23°C and 50%RH, a 2kg roller was reciprocated once, and the other adhesive surface of the above-mentioned measurement sample was pressed against the surface of the stainless steel plate (SUS304BA plate) obtained by washing with ethyl acetate. It was placed under the same environment for 72 hours, and then a universal tensile compression tester was used. According to JIS Z 0237:2000, the peel strength (adhesion to SUS) [N / 25mm] was measured under the conditions of a tensile speed of 300 mm / min and a peeling angle of 180 degrees. In the measurement of the above-mentioned peel strength, as a universal tensile compression tester, a "tensile compression tester, TG-1kN" manufactured by Minebea or its equivalent can be used. It should be noted that when the single-sided PSA sheet is subjected to the above-mentioned peel strength measurement, it is not necessary to use a PET film as a backing. When the substrate thickness is thin (for example, when the substrate thickness is 25 μm or less), a PET film as a backing may be used.

[0282] [Impact resistance test (pendulum)]

[0283] The impact resistance (impact adhesive strength) [J / cm 2 ]. As the test piece, the substrate-free double-sided adhesive sheet of each example was cut into 10 mm square adhesive sheets, and a 10 mm square, 5 mm thick stainless steel (SUS304) plate was pressed and bonded to another stainless steel plate (SUS304 plate) at a load of 35N for 10 seconds, and then cured at room temperature for 48 hours. The measurement was carried out under the conditions of hammer energy 2.75J and hammer speed (impact speed) 3.5m / sec.

[0284] [Resilience resistance test in Z-axis direction (high temperature and high humidity conditions)]

[0285] like Figure 5 As shown in (a), a polycarbonate (PC) plate 50 having a length of 30 mm, a width of 10 mm, and a thickness of 2 mm and a PET film 60 having a length of 70 mm, a width of 10 mm, and a thickness of 75 μm are prepared, and the PC plate 50 and the PET film 60 are overlapped in such a manner that one end in the longitudinal direction of the PC plate 50 and the PET film 60 are aligned, and the PC plate 50 and the PET film 60 are fixed in a state where the remaining part of the PET film 60 protrudes from the other end of the PC plate 50. A commercially available double-sided adhesive tape (manufactured by Nitto Denko Corporation, "No. 5000 NS") is used for the above fixing.

[0286] The adhesive sheet of each example with both adhesive surfaces protected by two release liners was cut into a size of 3 mm in width and 10 mm in length, thereby preparing an adhesive sheet sample piece 70. The surface of the PC board 50 on the side opposite to the fixed surface of the PET film was set as the upper side, and one release liner was peeled off from the above-mentioned adhesive sheet sample piece 70, so that the width direction of the PC board 50 was consistent with the length direction of the adhesive sheet sample piece 70, and the adhesive sheet sample piece 70 was adhered and fixed to the upper surface of the PC board 50 in a manner that the two ends of the width direction of the adhesive sheet sample piece 70 were located on the line of 7 mm and 10 mm from the other end on the upper surface of the PC board 50. The above-mentioned fixing was performed by reciprocating a 2 kg roller once on the upper surface of the adhesive sheet sample piece 70 protected by the other release liner.

[0287] Next, under an environment of 23° C. and 50% RH, the other release liner of the adhesive sheet sample piece 70 attached to the PC board 50 was peeled off. Figure 5As shown in (b), the protruding portion (length 40 mm) of the PET film 60 fixed to the PC board 50 protruding from the PC board 50 is folded back toward the PC board 50 side, so that the adhesive sheet sample piece 70 is aligned with the other end (free end) of the PET film 60, and a 0.1 kg roller is reciprocated once on the PET film 60, thereby fixing the other end of the bent PET film 60 to the upper surface of the PC board 50 via the adhesive sheet sample piece 70, and exposing it to an environment of 65°C and 90% RH. After being exposed to this environment for 72 hours, it is confirmed whether the adhesive state of the adhesive sheet sample piece 70 and the PET film 60 is maintained, as shown in FIG. Figure 5 As shown in (c), the peeling of the PET film 60 is judged as "peeling". While the PET film 60 is maintained, the protrusion height [mm] of the PET film 60 from the adhesive sheet sample piece 70 is measured using a microscope. The measurement is performed 3 times, and the lowest value is recorded. It should be noted that the above-mentioned protrusion height is the height including the thickness of the adhesive sheet sample piece 70.

[0288] This evaluation method is different from the conventional repulsion resistance evaluation in that the repulsion resistance of the adhesive sheet can be evaluated under harsh conditions of high temperature and high humidity, such as 65°C and 90% RH, for a peel load substantially only in the thickness direction (Z-axis direction). Furthermore, by observing the repulsion resistance over time, the continuous repulsion resistance can be evaluated.

[0289] Table 1 shows the outline and evaluation results of the PSA sheet of each example.

[0290]

[0291] As shown in Table 1, the adhesives of Examples 1 to 6 contain acrylic polymers as monomer components, have a storage modulus G' of 20,000 Pa or more at 65°C, and a tan δ of 0.3 or more at -20°C. The results of the impact resistance test of the adhesive sheets of Examples 1 to 6 are 0.3 J / cm 2 As shown above, the ridge height of the resilience test in the Z-axis direction is less than 2.0 mm. In contrast, the adhesive of Comparative Example 1 does not contain heptyl acrylate, but contains an acrylic polymer containing 2EHA as the main monomer, and the storage modulus G' at 65°C is less than 20,000 Pa, and it cannot withstand the resilience test in the Z-axis direction. The storage modulus G' of the adhesive of the adhesive sheet of Comparative Examples 3 to 4 is also less than 20,000 Pa at 65°C, and it peels off in the resilience test in the Z-axis direction (Comparative Example 3), or the ridge height of the resilience test in the Z-axis direction is larger than that of Examples 1 to 6. In addition, the adhesive of Comparative Example 2 does not contain heptyl acrylate, but contains an acrylic polymer containing BA as the main monomer, and the tanδ at -20°C is less than 0.3, and the result of the impact resistance test is a value lower than that of Examples 1 to 6.

[0292] Although specific examples of the present invention have been described in detail above, these are merely illustrative and do not limit the claims. The technology described in the claims includes various modifications and changes to the specific examples described above.

[0293] Description of symbols

[0294] 1, 2, 3 adhesive sheets

[0295] 10 Support substrate

[0296] 10A first side

[0297] 10B Second side (back side)

[0298] 21 Adhesive layer (first adhesive layer)

[0299] 21A bonding surface (first bonding surface)

[0300] 21B Second adhesive surface

[0301] 22 Adhesive layer (second adhesive layer)

[0302] 22A bonding surface (second bonding surface)

[0303] 31, 32 Release liner

[0304] 100, 200, 300 adhesive sheets with release liner

Claims

1. An adhesive sheet, wherein: The pressure-sensitive adhesive sheet comprises a pressure-sensitive adhesive layer containing an acrylic polymer. The acrylic polymer is a polymer containing a monomer component of heptyl acrylate, The adhesive layer has a storage modulus G' of 20000 Pa or more at 65°C and a tan δ of 0.3 or more at -20°C, Here, the tan δ refers to the ratio of the loss modulus G" to the storage modulus G' of the adhesive layer (G" / G').

2. The adhesive sheet according to claim 1, wherein The weight average molecular weight of the acrylic polymer is 700,000 or more.

3. The adhesive sheet according to claim 1 or 2, wherein The glass transition temperature of the adhesive layer is in the range of -15°C to 15°C, Here, the glass transition temperature of the pressure-sensitive adhesive layer refers to the glass transition temperature obtained from the peak temperature of tan δ in dynamic viscoelasticity measurement.

4. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein The adhesive layer further comprises a tackifying resin.

5. The adhesive sheet according to claim 4, wherein The tackifying resin is at least one selected from rosin-based tackifying resins and terpene-based tackifying resins.

6. The adhesive sheet according to claim 5, wherein The content of the tackifier resin in the pressure-sensitive adhesive layer is 70 parts by weight or less based on 100 parts by weight of the acrylic polymer.

7. The pressure-sensitive adhesive sheet according to any one of claims 1 to 6, wherein The adhesive layer further includes an acrylic oligomer.

8. The pressure-sensitive adhesive sheet according to any one of claims 1 to 7, wherein The adhesive composition for forming the adhesive layer includes at least one selected from an isocyanate-based crosslinking agent and an epoxy-based crosslinking agent.

9. The pressure-sensitive adhesive sheet according to any one of claims 1 to 8, wherein The adhesive sheet has a 180-degree peel strength to a stainless steel plate of 20 N / 25 mm or more.

10. The pressure-sensitive adhesive sheet according to any one of claims 1 to 9, wherein The adhesive sheet is used for fixing components in portable electronic devices.

Citation Information

Patent Citations

  • Fixing structure for physical quantity sensor

    JP2022108023A

  • Adhesive agent, adhesive tape, electrical appliance, onboard member, and securing method

    WO2021125247A1

  • Adhesive agent composition, adhesive tape, affixing method for electronic device component or in-vehicle component, and production method for electronic device component or in-vehicle component

    WO2021125278A1

  • Acrylic adhesive composition and adhesive sheet

    CN109628026A

  • Adhesive agent, adhesive tape, and method for affixing electronic components or vehicle-mounted components

    CN111868194A